An event-related potentials account of brain predictive coding - Carlos M. Gómez; Antonio Arjona; Francisco J. Ruíz-Martínez; Manuel Muñoz-Caracuel; Vanesa Muñoz; Elena I. Rodriguez-Martinez (Cognitive Neurodynamics, 2026)
Predictive coding is a theory that tries to account for how the brain processes in an anticipatory manner the expected stimuli, and reorganizes the underlying neural networks as a consequence of the outcome of predictions: Correct or incorrect. EEG has the advantage of making a continuous and almost instantaneous record of brain activity. The present report summarizes work on Event-Related Potentials (ERPs) and reviews the neural validity of Predictive processing as a mechanism to predict future events, assess the validity of predictions, and then update the probabilities associated with future events. Using two experimental models: predictive tone sequences and central cue Posner paradigms and Bayesian modelling, the report suggests that Contingent Negative Variation (CNV) would be related to prior expectation, Mismatch negativity (MMN) and P300 to Bayesian surprise and/or prediction error, and Post Imperative Negative Variation (PINV) to the assessment of trial outcome in uncertainty situations. The review tends to support predictive coding as a theory consistent with brain operations indexed by ERPs.

Dry-fractionated Amylaceous pea flour for phosphate reduction in mortadella: Technological, oxidative and sensory impacts during refrigerated storage - Géssica Hollweg; Jaqueline Graziela de Oliveira Zuchetto; Andressa Inês Schú; Bibiana Alves dos Santos; Maximiliano Segundo Escalona Jiménez; Matheus Abraão Piovesan Pedroso; Alexandre José Cichoski; Jose Manuel Lorenzo Rodriguez; Viviani Ruffo de Oliveira; Paulo Cezar Bastianello Campagnol (Meat Science, 2026)

Ant pruning and weak tussock facilitation jointly shape planted sapling performance along an elevation gradient - Daniel Renison; Juan Manuel Rodriguez; Santiago Costas; Niklas Heinemann; Isabell Hensen (Forest Ecology and Management, 2026)

Using fracture scarp intersection lineations as kinematic indicators on active normal fault scarps - Billy J. Andrews; Zoë K. Mildon; Manuel L. Diercks; Sam Mitchell; Gerald P. Roberts; Constanza Rodriguez Piceda; Jenni Robertson (Journal of Structural Geology, 2026)

Electromethanogenesis from H2S containing biogas: H2S and cathode potential drive microbial selection and methane yields - Ankit Rao; Manuel Guillermo Rodriguez Ancieta; Chrystelle Bureau; Cedric Midoux; Jean-Marie Fontmorin; Eleftheria Ntagia (Bioresource Technology Reports, 2026)

Spatial associations of Aboriginal and Torres Strait Islander populations with climate exposure, green cover, and socioeconomic advantage in New South Wales, Australia - Manuel Esperon-Rodriguez; Rossano Schifanella; Alessio Russo; Diego Esperon-Rodriguez; Mahmuda Sharmin; Peta Jeffries; Mark G. Tjoelker (Regional Environmental Change, 2026)
Urban areas face growing climate pressures from projected heat increases and rapid urbanisation, yet empirical studies assessing Indigenous population distributions relative to climate exposure and green infrastructure remain scarce. This study examines spatial associations between Aboriginal and Torres Strait Islander population sizes and urban environmental conditions across 614 urban areas in New South Wales, Australia, testing whether expected patterns of climate and green space marginalisation are evident. Using Generalised Additive Mixed Models, we quantified relationships with projected heat exposure (ΔMTWM), green cover percentage, green space accessibility, total population size, and socioeconomic advantage (Index of Relative Socio‑economic Advantage and Disadvantage, IRSAD), contrasting Aboriginal versus non‑Aboriginal population patterns using identical model parameters. Contrary to marginalisation expectations, Aboriginal populations showed positive non‑linear associations with higher ΔMTWM, greater green cover and larger total population size, and a positive linear relationship with IRSAD. Green cover significantly influenced Aboriginal, but not non‑Aboriginal, population distributions, while accessibility showed no significant associations for either group. Regional variation explained substantial additional variation in population distributions. These unexpected co‑location patterns challenge simple disadvantage narratives, revealing complex spatial dynamics potentially driven by historical settlement, contemporary planning or cultural preferences. These findings highlight the need for fine-scale, longitudinal and community research to inform urban climate adaptation planning. Our study emphasises the importance of considering local context and interacting factors when assessing climate change exposure and designing adaptation policies for Indigenous communities.

Climate variability and air pollution threaten urban tree growth in a tropical city - Naeem Bin Mohammad; Jannatul Ferdous Rahi; Md. Qumruzzaman Chowdhury; Md. Imam Hossain Imran; Manuel Esperon-Rodriguez; Mahmuda Sharmin (Urban Ecosystems, 2026)

Coupling generative and predictive machine learning algorithms to enhance haloacetonitriles prediction in small water systems - Chengfeng Cao; Yixiang Zhou; Guangji Hu; Manuel J. Rodriguez; Kasun Hewage; Rehan Sadiq (Journal of Hazardous Materials, 2026)

Signal of phenotypic plasticity in the population dynamics of the crab Microcassiope xantusii across Pocillopora-dominated coral reefs - Sandra Rodriguez-Huezo; Manuel Ayon-Parente; Arizbeth Alonso-Dominguez; Fabian Alejandro Rodriguez-Zaragoza; Ignacio Caceres (Hydrobiologia, 2026)

Transforming lignocellulosic residues into bio-lactic and bio-succinic acid: A comparative sustainability analysis using a hybrid life cycle approach - Silvia Rodriguez-Fernandez; Ismael Díaz; Manuel Rodríguez (Biomass and Bioenergy, 2026)

Bioethanol Production from Sugarcane Bagasse Pyrolytic Sugar Using Immobilized Yeasts in Unconventional Bioreactor Assisted by Magnetic Field - Geraldo Ferreira David; Cristilane Macharete de Andrade; Victor Haber Perez; Diana Catalina Cubides-Roman; Thays da Costa Silveira; Oselys Rodriguez Justo; Manuel Garcia-Perez (Sugar Tech, 2026)
The novelty of this study lies in the integration of fermentation in a magnetically stabilized fluidized bed bioreactor with S. cerevisiae supported on calcium alginate with magnetic particles and using levoglucosan, a pyrolytic sugar from sugarcane bagasse, as a substrate for bioethanol production. Sugarcane bagasse was pretreated with acetic acid to remove alkali/alkaline earth metals (AAEMs) aiming to intensify levoglucosan production in the bio-oil prior pyrolysis at 400 °C in an Auger reactor. Subsequently, the levoglucosan extracted from the bio-oil was hydrolyzed with H₂SO₄ and partially detoxified to use the resulting extract as substrate. Fermentations were carried out in the bioreactor operating in magnetically stabilized bed mode with axial magnetic field lines at 12 kA/m. The fermentation kinetics were monitored by substrate consumption and ethanol production over 8h under anaerobic conditions. When glucose was used as substrate (control experiments), the results revealed that the magnetic field induced a higher sugar consumption rate and bioethanol productivity of 5.8 gL −1 h −1 , achieving a fermentative efficiency of 97.44%, since the fermentation time was reduced by approximately 2h compared to fermentations without the application of a magnetic field. However, when hydrolyzed levoglucosan extract was evaluated, the fermentative efficiency was 91.57%, approximately 6.5% lower when compared to the control experiment. This could occur due to the presence in the fermentation medium of traces of pyrolytic derivatives, which are known inhibitors of cellular activity. Furthermore, the stimulatory effect of the magnetic field on process productivity is consistent with data previously reported in studies with yeast cells during alcoholic fermentations, thus corroborating the potential of this technology as an alternative process for bioethanol production on a bench scale.

Investigating multi-scale associations and thresholds between eco-environment quality and urban landscape patterns: A case from coastal China - Linsheng Wen; Manuel Esperon-Rodriguez; Yun Peng; Aifang Weng; Yunrui Zhou; Sunbowen Zhang; Baoyin Li; Yuying Lin (Journal of Geographical Sciences, 2026)

Limitations of quantified rules in urban forestry - Peter Duinker; Christian Messier; Manuel Esperon-Rodriguez; Suzanne Mavoa; Jürgen Bauhus (Landscape and Urban Planning, 2026)

Dialogue between science, law, and traditional knowledge regarding global environmental problems - Manuel Alejandro Lizardi-Jiménez; Violeta Mendezcarlo Silva; María Suhey Tristán Rodriguez; Guillermo Luevano Bustamante; Gabriela Josefina Aguirre-García (Journal of Environmental Management, 2026)

Indirect exposure to organophosphate pesticides and its possible growth disorders in children of farmers in Northwest Mexico - Estefanía Ochoa-Ruiz; Aarón Israel Moreno-García; Daniel Alejandro Licea-Espinoza; Gisela Pineda-García; Krysta Paola Carranza-Ambriz; Kenya Karina Soto-Rodriguez; Arnold García-Ledezma; José Manuel Cornejo-Bravo; Ana Laura Martínez; Eleonora Mondani; Aracely Serrano-Medina (International Archives of Occupational and Environmental Health, 2026)
Purpose This study investigated the correlation between growth disorders and indirect pesticide exposure in children of farmers. Methods A cross-sectional study was conducted with 134 children of farmers occupationally exposed to organophosphate pesticides in the ejido Venustiano Carranza, an agricultural community in San Quintín, Baja California, Mexico. These children were compared with a control group of 56 unexposed children. Anthropometric measurements and biochemical analyses were performed in both groups to evaluate renal, hepatic, and nutritional profiles. Hormonal profiles were quantified using ELISA techniques. Cholinesterases are quantified using known colorimetric methods. Food security was also analyzed through a dietary diversity study, focusing on households. Results Indirectly exposed group showed a higher prevalence of stunting (18% vs. 16.4%) than controls. Food safety was adequate in both groups (X 2 = 1.88, p = 0.597). The indirectly exposure children showed significantly higher calcium levels (9.99 ± 0.63 mg/dL) and significant increases in liver enzymes AST and GGT ( p < 0.001). ALP was 1.5 times lower than in unexposed children ( p < 0.001), showing a strong association with exposure time ( p = 0.009). The indirectly exposed group showed lower GH and IGF-1 levels; 2.55 and 1.28 times lower than in controls, respectively. Children with indirect exposure showed a significant reduction in AChE (7211 ± 1917 vs. 8368 ± 213 U/L, p < 0.001) and an even greater decrease in BChE (6426 ± 1664 vs. 8025 ± 1462 U/L, p < 0.001). Conclusion This work demonstrates an association between environmental exposure to organophosphate pesticides and children's growth and provides crucial insights for future research and policymaking.

Evaluation of the Impact of Environmentally Driven Curtailment Regulations on Wind Farm Energy Production - Javier Serrano González; Ángel Gaspar González Rodriguez; Antonio Gómez Expósito; Jesús Manuel Riquelme Santos (Environmental Modeling & Assessment, 2026)
Environmentally driven curtailment strategies—based on increasing wind turbine cut-in speeds during high bat activity—are increasingly adopted in wind energy regulations worldwide. These measures, typically enforced during summer nights, aim to reduce bat mortality but lead to energy losses that can compromise the economic performance of wind farms. This study assesses the impact of such regulations by analyzing three key variables that influence curtailed energy: mean wind speed, wind variability, and turbine design, characterized through specific power (the ratio of rated power to rotor swept area). A combined approach is proposed, integrating a theoretical energy model with real performance data from 130 commercial wind turbines, enabling a comprehensive evaluation across a wide range of wind regimes and turbine configurations. The results show that curtailed energy increases significantly at low-wind sites and for turbines with lower specific power. Wind variability also has a notable influence, with contrasting effects depending on the wind class. Although the study is based on the regulatory framework under development in Spain, the methodology is generalizable to other regions. The findings provide valuable insights for developers and policymakers, supporting the design of strategies that balance biodiversity conservation with the economic sustainability of wind energy deployment.

Impact of different cryopreservation protocols on epididymal sperm quality and subsequent in vitro embryo production in domestic cats - Ana Munoz-Maceda; Andrea Priego-Gonzalez; Sandra Barroso-Arévalo; Jorge Hernández-Matarazzo; Carolina Cuevas-Ruiz; Joaquín Cerdeira; Eduardo de Mercado; Manuel Álvarez-Rodríguez; Ana Sanchez-Rodriguez; E.R.S. Roldan; M.J. Sánchez-Calabuig (Theriogenology, 2026)

Cultural adaptation and psychometric properties of the canine owner-reported quality of life questionnaire (CORQ) for assessing quality of life in dogs with cancer - Manuel Fuertes-Recuero; Paula Rodriguez-González; María Suárez-Redondo; Miriam Portero; Andrés Yzuel; Silvia Penelo; Carmen Pérez; Elena Martínez de Merlo; Michelle A. Giuffrida; Gustavo Ortiz-Díez (The Veterinary Journal, 2026)

Reduction of frosty pod rot severity in Theobroma cacao CCN51 by indigenous Trichoderma-based bioformulations under controlled conditions - Anthony Apolinario Cortez-Lázaro; Ramiro Esteban Rodriguez; Ingrid Milagros Iliquin-Inga; Jorge Ronny Diaz-Valderrama; Santos Triunfo Leiva-Espinoza; Edwin Hualpa-Cutipa; Segundo Manuel Oliva-Cruz; Liz Marjory Cumpa-Velasquez (Fungal Biology, 2026)

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Comparison of the processes photo-Fenton and photocatalysis with TiO2 supported on non-woven fabric using a LED radiation in the degradation of the pharmaceutical meloxicam - Graziele Elisandra do Nascimento; José Petrúcio Martins Barbosa; Raissa Aguiar de Freitas; Pollyanna Michelle da Silva; Patrícia Maria Guedes Paiva; Ramón Raudel Pena Garcia; Joan Manuel Rodriguez-Diaz; Marta Maria Menezes Bezerra Duarte (Environmental Science and Pollution Research, 2026)

Nanoplastics internalization impairs mitochondrial activity in equine sperm - Sofia Dindo; Laura Tovar-Pascual; Vito Antonio Baldassarro; Diego Bucci; Beatrice Mislei; Marcella Spinaci; Jose Manuel Ortiz-Rodriguez (Theriogenology, 2026)

Population dynamics and somatic production of burrowing shrimp assemblage in a Mexican estuary under ENSO-driven temperature fluctuations - Ignacio Caceres; Omar Hernando Avila-Poveda; Sandra Rodriguez-Huezo; Fabian Alejandro Rodriguez-Zaragoza; Manuel Ayon-Parente (Regional Studies in Marine Science, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Effect of polystyrene nanoplastics on in vitro maturation of pig cumulus-encosed oocytes - Marcella Spinaci; Sofia Dindo; Nadia Govoni; Laura Tovar; Alessandro Marino Volsa; Cinzia Cappannari; Diego Bucci; Jose Manuel Ortiz-Rodriguez (Research in Veterinary Science, 2025)

Coupled effect of pyrolysis temperature and HNO3 pretreatment on sugarcane bagasse fast pyrolysis for levoglucosan production - Geraldo Ferreira David; Rodolfo Roberto Moreno-Parra; Victor Haber Perez; Thays da Costa Silveira; Euripedes Garcia Silveira Junior; Oselys Rodriguez Justo; Manuel Garcia-Perez (Biomass and Bioenergy, 2025)

An integrative urban tree risk index as a novel framework for risk assessment: A case study of Montreal, Canada - Manuel Esperon-Rodriguez; Annick St-Denis; Julie Messier; Rachael V. Gallagher; Mark G. Tjoelker; Christian Messier (Urban Forestry & Urban Greening, 2025)

Determination of flowering stage based on artificial intelligence and the daily weight of bee hives - Andrés Gersnoviez; Francisco J. Rodriguez-Lozano; María Brox; José Moreno-Carbonell; Manuel Ortiz-Lopez; José M. Flores (Computers and Electronics in Agriculture, 2025)

Quality-by-design and current good practices for the production of test and reference materials for micro- and nano-plastic research - Korinna Altmann; Lukas Wimmer; Victor Alcolea-Rodriguez; Tassilo Waniek; Volker Wachtendorf; Kay Matzdorf; Dmitri Ciornii; Petra Fengler; Frank Milczewski; Itziar Otazo-Aseguinolaza; Manuel Ferrer; Miguel A. Bañares; et al. (Journal of Hazardous Materials, 2025)

Gene dysregulation impairs placental angiogenesis in allogeneic pig pregnancies - Cristina A. Martinez-Serrano; Josep M. Cambra; Manuel Alvarez-Rodriguez; Inmaculada Parrilla; Cristina Cuello; Maria A. Gil; Emilio A. Martinez; Heriberto Rodriguez-Martinez (Animal Reproduction Science, 2025)

A methodology for coagulant virtual testing to improve dissolved organic matter removal in surface water treatment - Christian Ortiz-Lopez; Christian Bouchard; Manuel J. Rodriguez (Science of The Total Environment, 2025)

Understanding urban tree heat and drought stress by tracking growth and recovery following an extreme year - Renée M. Marchin; Manuel Esperon-Rodriguez; Mark G. Tjoelker; David S. Ellsworth (Landscape and Urban Planning, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Tree survival and growth in the highlands of central Argentina: Impact of wildfires and land management - Daniel Renison; Iván Barberá; Ana M. Cingolani; Juan Manuel Rodriguez; Isabell Hensen (Forest Ecology and Management, 2025)

Global trends in urban forest irrigation: Environmental influences, challenges and opportunities for sustainable practices across 109 cities worldwide - Manuel Esperon-Rodriguez; Rachael V Gallagher; Alessio Russo; Sally A Power; Pedro Calaza-Martínez; Tiago Capela Lourenço; Paloma Cariñanos; Ana Alice Eleuterio; Zhengfei Guo; Gervais Lee; Pierre Masselot; Robert I. Mcdonald; et al. (Sustainable Cities and Society, 2025)

Wavelet analysis and sinusoidal modelling of environmental variables in a weaned piglet farm - Maria D. Fernandez; Manuel R. Rodriguez; Xose R. Fdez-Vidal; Roberto Besteiro (Building and Environment, 2025)

Response to Guerin et al. Comment on ’Mapping the climate risk to urban forests at city scale’ - Manuel Esperon-Rodriguez; Rachael Gallagher; Niels Souverijns; Quentin Lejeune; Carl-Friedrich Schleussner; Mark G. Tjoelker (Landscape and Urban Planning, 2025)

Urban Tree Growth and Drought Responses Show Evidence of Climate Resilience - Manuel Esperon‐Rodriguez; Matthew Brookhouse; Sally A. Power; Diego Avi; Thomas Baer; Paul D. Rymer; Mark G. Tjoelker (Global Change Biology, 2025)
Climate change has a negative impact on the vitality of forests, and drought and heatwaves are the most influential abiotic stressors that contribute to tree health decline and mortality. Urban trees are not only vulnerable to climate change, but they also face harsh environmental conditions, including the urban heat island effect, limited soil volume and water availability. Therefore, the long‐term sustainability of urban forests relies on healthy and thriving trees and the identification of species that are resilient to climate change. Thus, it is fundamental to understand how urban trees respond to environmental conditions, including climate. This study investigates how urban trees respond to both long‐term climatic conditions and episodic extreme climate events. We evaluated variation in urban tree growth across differing climates by reconstructing growth histories and developing drought response indices. We selected 10 tree species planted in seven cities distributed along temperature and precipitation gradients across the Australian continent. We determined spatial and temporal patterns of tree‐ring growth in relation to extreme climate events. We found significant differences among cities, suggesting that local environmental conditions significantly influence tree growth. While some species showed fast annual growth in cool and wet cities, other species had similar growth across all cities or even faster growth in hot and dry cities. Urban trees generally responded positively to wetter conditions during the warmest month, which might be related to longer growing seasons and water availability. We found a positive effect of extreme hot conditions on growth, suggesting that urban trees might be well adapted to warm urban environments. Species climate‐growth relationships can help guide species selection to maximize benefits delivered by urban forests and minimize environmental and socio‐economic losses under current and future climates.

Socio-economic factors, climate, and people’s behaviours determine urban tree health - Manuel Esperon-Rodriguez; Mahmuda Sharmin; Diego Esperon Rodriguez; Christian Messier; Jens-Christian Svenning; Sophie Moore; Mark G. Tjoelker (Urban Forestry & Urban Greening, 2025)

Biocontrol and plant growth-promoting activities of airborne bacteria - Beatriz G. Guardado-Fierros; Miguel A. Lorenzo-Santiago; Manuel R. Kirchmayr; Olga A. Patrón-Soberano; Jacobo Rodriguez-Campos; Silvia M. Contreras-Ramos (World Journal of Microbiology and Biotechnology, 2025)

Platelet Analysis in the Thrombus Plus Serum BNP for Detecting Clot-Related Atrial Fibrillation. Results From the ITACAT Multicentric Registry - Jorge Pagola; Jesus Juega; Laura Dorado; Maria Hernandez-Perez; Carlos Lazaro; Alvaro Garcia-Tornel; Marta Olive; Manuel Requena; Marta Rubiera; Marian Muchada; Noelia Rodriguez-Villatoro; David Rodriguez-Luna; et al. (Translational Stroke Research, 2025)

Impact of climate change on the hydrological regime in a small watershed of the tropical Andean Plateau - Darwin Mena-Rentería; Carlos Peña-Guzmán; Ronal Sierra; Manuel Rodriguez (Sustainable Water Resources Management, 2025)
This study evaluated the impact of climate change on the hydrological regime of a small watershed in the Tropical Andean Plateau in Colombia. We used modeling tool Hydro-BID, a specialized software with hydrological and climatic modules that can evaluate the hydrological processes to generate models. This tool has the potential to inform water resource management and planning in Latin America and the Caribbean. To simulate future hydrologic flows, we selected the MOI-ESM-MR-CORDEX model for precipitation and the MOI-ESM-MR model for temperature. Projections for precipitation and temperature on a reduced scale were calculated using a method based on chaos theory for three representative concentration pathway (RCP) scenarios designated 2.6, 4.5, and 8.5 based on global climate models (GCMs) and regional climate models (RCMs). The results of the calibration process showed that the evaluated hydrological parameters are better represented by the model at a monthly scale. In addition, the climate change model showed an estimated increase in the average streamflow of 2.1% to 6% compared to a base scenario that represented current conditions (1.22 m 3 s −1 ), with flow rates of 1.28 m 3 s −1 , 1.24 m 3 s −1 , and 1.29 m 3 s −1 for RCPs 2.6, 4.5, and 8.5, respectively. These values, associated with a significant increase in precipitation and a decrease in temperature, are expected for the Tropical Andean Plateau watersheds of Colombia. The results obtained in this study are useful for water resource planners and policy makers, especially for the management of water supply infrastructure, flood risk, and agricultural productivity in the area.

Experimental validation of computationally predicted phytoene synthase isoforms encoded by the Arabidopsis thaliana PSY gene - Juan Navarro-Carcelen; Manuel Rodriguez-Concepcion (Plant Cell Reports, 2025)
Key message The representative model in the TAIR database of the first and main rate-determining enzyme of the carotenoid pathway, phytoene synthase (PSY), corresponds to a computational prediction artifact.

INIA 333 – CHUGAYNA new Potato Variety Resilient to Climate Change for the Family Farming System with Tolerance to Frost, Resistant to Late Blight and high Quality for Fresh Consumption - Héctor Cabrera; Ronal Otiniano; Rosemeri Pando; Henry Sánchez Garcia; Willian Huamanchay Rodriguez; Juan M. Pérez; Stef de Haan; Manuel Gastelo (American Journal of Potato Research, 2025)
The new potato variety INIA 333–CHUGAYNA, is the result of the joint work of the NGO Asociación Pataz, INIA and the International Potato Center, it was generated through traditional breeding and the use of the participatory varietal selection methodology, as a variety resilient to climate change with frost tolerance, resistance to late blight, compared to the improved variety INIA 302-Amarilis and the native varieties, Huevo de Indio. This new variety is also resilient to climate change, tolerant to frost, with field resistance to late blight, high tuber yield, low glycoalkaloid content and high quality for fresh consumption, adapted up to 4000 m above sea level. It was released in 2023 and officially registered in the national registry of commercial varieties of Peru. The new variety INIA 333-CHUGAYNA requires minimal use of fungicides and has a high economic profitability that will improve the living standards of small and medium-sized farmers in Peru. It can also be used as a parent in breeding programs in other countries in development, to confront climate change, especially frost.

Social and knowledge diversity in forest education: Vital for the world’s forests - Mika Rekola; Andrew B. Taber; Terry L. Sharik; John A. Parrotta; Michael J. Dockry; Folaranmi D. Babalola; Tara L. Bal; David Ganz; Marta Gruca; Manuel R. Guariguata; James Kungu; Pipiet Larasatie; et al. (Ambio, 2025)
A global assessment of the status of tertiary, vocational, and technical forest education and training found deficits in inclusion of knowledge and student diversity. Coverage of forest services and cultural and social issues was characterized as weak in the curricula of many programs. The inclusion of traditional and Indigenous knowledge was frequently poor or absent. Gaps were found in enrollment at tertiary education levels with respect to diversity by gender, race/ethnicity, and other societal groups. If unaddressed, forest researchers, professionals, and workers will continue to lack familiarity with different knowledge systems and the importance of inclusive representation. Improvements in forest education related curricula, research, monitoring, policy, recruitment, and promotion are recommended. Without remedial action to build a representative, skilled, and knowledgeable workforce, prospects for forests to meet local, national, and global goals are at risk. Improved social and knowledge diversity in forest education is paramount for the future of forests.

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

A nation-wide urban trial network of tree and shrub climate resilience - Manuel Esperon-Rodriguez; Sally A. Power; Mark G. Tjoelker; Mahmuda Sharmin; Paul D. Rymer (Urban Forestry & Urban Greening, 2025)

Balancing supply security and decarbonization: Optimizing Germany’s LNG port infrastructure under the European Green Deal - Per J. Agrell; Henri Dehaybe; Manuel Herrera Rodriguez (Energy Policy, 2025)

Exploring Construction and Demolition Waste as a Sustainable Adsorbent for Efficient Removal of AB113 Dye from Aqueous Solutions - Brahim Arhoun; Maria del Mar Cerrillo-Gonzalez; Maria Villen-Guzman; Juan Manuel Paz-Garcia; Jose Miguel Rodriguez-Maroto (Water, Air, & Soil Pollution, 2025)
An innovative approach to the treatment of textile wastewater by utilizing fine fractions of construction and demolition waste (CDW) as a cost-effective adsorbent is presented in this work. Through batch experiments, the impact of key parameters on the adsorption process was explored, identifying optimal conditions: natural pH, adsorbent dosage (S/L) of 20 g L −1 , and temperature of 20 °C. The characterization of CDW was performed using ICP, BET, FTIR, SEM–EDX, XPS, and XRD. The kinetics of adsorption were effectively described by the Elovich model, while equilibrium adsorption data showed good agreement with the Freundlich model. The maximum monolayer adsorption capacity for acid blue AB113 dye on CDW obtained from Langmuir isotherm was 89.52 mg g –1 . Thermodynamic analysis indicated an exothermic and feasible nature of the adsorption process. The results of this study highlight the potential use of fine CDW as a promising adsorbent to remove acid blue113 dye from textile wastewater. Graphical Abstract

Perceptions and Attitudes of Drinking Water Supply Systems Staff Towards Climate Change Adaptation for Drinking Water Quality Management - S. M. Cynthia Compaoré; Ianis Delpla; Sonja Behmel; Manuel J. Rodriguez (Environmental Processes, 2025)

Prognosis impact and clinical findings in renal cancer patients: comparative analysis between public and private health coverage in a cross-sectional and multicenter context - Eduardo Barrera-Juarez; Antonio Nassim Halun-Trevino; Manuel Ruelas-Martinez; Andres Madero-Frech; Victor Camacho-Trejo; Miguel Estrada-Bujanos; David Bojorquez; Jhonatan Uribe-Montoya; Francisco Rodriguez-Covarrubias; Cynthia Villarreal-Garza (Cancer Causes & Control, 2025)
Purpose Research on disparities in prognosis and clinical characteristics between public and private healthcare sectors in developing countries remains limited. The study aimed to determine whether patients with public health coverage (1) have a greater mean tumor size at diagnosis compared to those with private health coverage; (2) exhibit differences in clinical staging and TNM classification between groups; and (3) show variations in demographic, clinical characteristics, histopathological findings, and surgical approaches among cohorts. Methods A cross-sectional, multicenter study was conducted on 629 patients from both private and public healthcare sectors, all histologically confirmed and surgically treated for Renal Cell Carcinoma (RCC), between 2011 and 2021 in high-volume hospitals in Monterrey, Mexico. To compare variables between groups, we employed independent samples t -tests, Mann Whitney U nonparametric test, along with Pearson’s chi-square test complemented by post hoc analyses. Results Mean tumor size in the public group was 1.9 cm greater than in the private group (7.39 vs. 5.51 cm, p < 0.001). Patients in the public sector more frequently presented with larger tumors, a higher prevalence of risk factors (excluding BMI and hypertension), advanced disease (OR 2.12, 95% CI 1.43–3.16, p < 0.001), presence of symptoms, elevated TNM, lymphovascular invasion and a lower prevalence of minimally invasive surgery. A male-to-female ratio of 2.6:1 was noted in the private coverage group. Conclusions This study highlights a notable association between public health coverage and a higher prevalence of advanced RCC, with tumors in private coverage patients being smaller yet larger than commonly reported. There is a crucial need to develop new health policies for early detection of renal cancer in developing countries.

SAmMD: The South American mineral deposit database - Guilherme Ferreira da Silva; Martín Ricardo Gozalvez; Alonso Arturo Marchena; Anderson Dourado Rodrigues da Silva; Braulio Ignacio Aguila Aravena; Diego Jesús Rodriguez; Eduardo Linares; Edwin Fernando Gallardo Vargas; Franco Drausin Pinzon Rivas; Guillermo Lopez Aguilera; Jose Amado Rondon Muñoz; Juan Manuel Turra; et al. (Journal of South American Earth Sciences, 2025)

Analysis of high-molecular-weight proteins using MALDI-TOF MS and machine learning for the differentiation of clinically relevant Clostridioides difficile ribotypes - Ana Candela; David Rodriguez-Temporal; Mario Blázquez-Sánchez; Manuel J. Arroyo; Mercedes Marín; Luis Alcalá; Germán Bou; Belén Rodríguez-Sánchez; Marina Oviaño (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The diurnal variation of dust and water ice aerosol optical depth at Jezero crater observed by MEDA/TIRS over a full Martian year - Michael D. Smith; Germán M. Martínez; Eduardo Sebastián; Mark T. Lemmon; Samuel A. Atwood; Daniel Toledo; Daniel Viúdez-Moreiras; Aurélien Stcherbinine; Jose Antonio Rodriguez-Manfredi; Manuel de la Torre Juárez (Icarus, 2025)

Preliminary insights into Red LED Irradiation for thawing cryopreserved boar semen - Laura Tovar; Diego Bucci; Marcella Spinaci; Ludovica Mammi; Barbara Merlo; Joan Enric Rodriguez Gil; José Manuel Ortiz Rodriguez (Animal Reproduction Science, 2025)

Capped honey segmentation in honey combs based on deep learning approach - Francisco J. Rodriguez-Lozano; Sergio R. Geninatti; José M. Flores; Francisco J. Quiles-Latorre; Manuel Ortiz-Lopez (Computers and Electronics in Agriculture, 2024)

The role of traditional NSAIDs and selective COX-2 inhibitors on COVID-19 outcomes: a real-world data study - Narmeen Mallah; Irene Visos-Varela; Bahi Takkouche; Rosendo Bugarín-González; María Piñeiro-Lamas; Teresa Herdeiro; Maruxa Zapata-Cachafeiro; Almudena Rodríguez-Fernández; Angel Salgado-Barreira; Adolfo Figueiras; Eduardo Carracedo-Martínez; Rosa M. García-Álvarez; et al. (Inflammopharmacology, 2024)

Analysis of stallion spermatozoa metabolism using Agilent Seahorse XFp Technology - Jose Manuel Ortiz-Rodriguez; Diego Bucci; Laura Tovar-Pascual; Silvia Granata; Marcella Spinaci; Salvatore Nesci (Animal Reproduction Science, 2024)

Diploid and triploid Chinook salmon ( Oncorhynchus tshawytscha ) exhibit differential immunological responses to acute thermal stress - Noah P. Rogozynski; Ivan G. Cadonic; Manuel Soto‐Dávila; Valentina Wong‐Benito; Tania Rodriguez‐Ramos; Paul Craig; Brian Dixon (Journal of Fish Diseases, 2024)
Exposure to temperatures outside of a fish's optimal range results in suppression of the immune system, ultimately leaving aquaculture stocks susceptible to disease outbreaks. This effect is exacerbated in triploid fishes, which demonstrate greater susceptibility to stress than their diploid counterparts. This study investigates the impacts of acute heat stress on the abundance of immune transcripts and proteins in diploid and triploid Chinook salmon ( Oncorhynchus tshawytscha ) , an important finfish crop. This study also demonstrates that acute heat stress induces significant increases in the abundance hsp70 , hsp90 and il1b transcripts in the head kidneys, gills and heart ventricles of both diploid and triploid Chinook salmon. Widespread dysregulation of antigen‐presentation transcripts was also observed in fish of both ploidies. These results suggest that acute heat stress activates acute‐phase responses in Chinook salmon and dysregulates antigen presentation, potentially leaving fish more susceptible to infection. At the protein level, IL‐1β was differentially expressed in the head kidney and ventricles of diploid and triploid salmon following heat shock. Differential expression of two tapasin‐like proteins in diploid and triploid salmon subjected to heat shock was also observed. Altogether, these data indicate that diploid and triploid Chinook salmon respond differently to acute thermal stressors.

A Multicriteria Model for the Assessment of Source Water Contamination by Anthropogenic Activities to Support Land Use Management - Ariane E. Marais; Irène Abi-Zeid; Manuel J. Rodriguez; Roxane Lavoie (Environmental Modeling & Assessment, 2024)

Reproductive physiology of the boar: What defines the potential fertility of an ejaculate? - Heriberto Rodriguez-Martinez; Cristina A. Martinez-Serrano; Manuel Alvarez-Rodriguez; Emilio A. Martinez; Jordi Roca (Animal Reproduction Science, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Development and characterization of a novel variant of long-acting bovine follicle-stimulating hormone (brscFSH) - Oscar Ignacio Cabeza; Natalie Parra; Rita Cerro; Rodrigo Mansilla; Roxana Zuniga Sanchez; Miguel Gutierrez-Reinoso; Eduardo H. Escribano; Raul Castillo; Lleretny Rodriguez-Alvarez; Kaio Tavares; Saul Gaudencio; Leonardo Martins; et al. (Theriogenology, 2024)

Exploring the nexus of urban form, transport, environment and health in large-scale urban studies: A state-of-the-art scoping review - Georgia M.C. Dyer; Sasha Khomenko; Deepti Adlakha; Susan Anenberg; Martin Behnisch; Geoff Boeing; Manuel Esperon-Rodriguez; Antonio Gasparrini; Haneen Khreis; Michelle C. Kondo; Pierre Masselot; Robert I. McDonald; et al. (Environmental Research, 2024)

Morphological changes in the fetal kidney induced by exposure to fluoride during pregnancy - Esaú Montañez-Rodriguez; Sabino Hazael Avila-Rojas; Ariana Guadalupe Jimenez-Dorantes; Juan Carlos León-Contreras; Rogelio Hernandez-Pando; José Manuel Arreola-Guerra; Casimiro Gerarduzzi; María Estela Meléndez-Camargo; Luz M. Del Razo; Olivier Christophe Barbier (Environmental Toxicology and Pharmacology, 2024)

Evaluating the impact of protected areas in lowering extinction risks in a biodiversity hotspot - Manuel Esperon-Rodriguez; Alex Correa-Metrio; Linda J. Beaumont; John B. Baumgartner; Jonathan Lenoir (Biological Conservation, 2024)

Mapping the climate risk to urban forests at city scale - Manuel Esperon-Rodriguez; Rachael V. Gallagher; Niels Souverijns; Quentin Lejeune; Carl-Friedrich Schleussner; Mark G. Tjoelker (Landscape and Urban Planning, 2024)

Optimizing sampling location for water quality degradation monitoring in distribution systems: Assessing global representativeness and potential health risk - Andres Ardila; Manuel J. Rodriguez; Genevieve Pelletier (Journal of Environmental Management, 2024)

A comparison of batch and semi-batch reactors for leaching battery cathodes (LiCoO2) under controlled addition of HCl and H2O2 - Maria del Mar Cerrillo-Gonzalez; Maria Villen-Guzman; Alvaro Rivas-Bascon; Jose Miguel Rodriguez-Maroto; Juan Manuel Paz-Garcia (Hydrometallurgy, 2024)

Hydroclimate variability in the Tropical Andes recorded by δ18O isotopes from a new network of Polylepis tarapacana tree-rings - Claudio Álvarez; Duncan A. Christie; Álvaro González-Reyes; Thomas T. Veblen; Gerhard Helle; Carlos LeQuesne; Milagros Rodriguez-Caton; Paul Szejner; Felipe Flores-Sáez; Tania Gipoulou-Zúñiga; Manuel Suazo-Álvarez; Tomás Muñoz-Salazar; et al. (Global and Planetary Change, 2024)

Spatio-temporal patterns in the biomass, species composition and nitrogen content of drift macroalgae in an urbanised coastal embayment - Juan Manuel Valero-Rodriguez; Tim Dempster; Wei Wen Wong; John A. Lewis; Perran L. M. Cook; Stephen E. Swearer (Journal of Applied Phycology, 2024)
Understanding spatio-temporal variability in the production of drift macroalgae is useful for monitoring and assessing the influence of local anthropogenic nutrient sources on coastal ecosystems. In this study we: (1) assessed how the drift macroalgal community composition and biomass have changed over a 22-year period in Port Phillip Bay (a large coastal embayment in Victoria, Australia); and (2) measured the amount of accumulated nitrogen in drift macroalgae and the contribution of anthropogenic nitrogen sources through isotopic analysis. The surveys revealed little overlap in species composition (<13%) and a significant decrease in standing stock biomass (from 631 to 49 g m -2 ) between surveys (1995/1996 and 2017/2018). This was associated with a high degree of turnover (β-diversity) at the genus level between surveys (mean – 0.53), resulting in distinct communities at all sites, particularly among red algal genera. In addition, the occurrence of ephemeral macroalgal blooms and a semi-perennial mat of the red macroalga Botryocladia sonderi at 10-15 m depth at locations close to nutrient sources indicate drift macroalgae are important nutrient accumulators in the bay. Isotopic analysis revealed a high contribution of anthropogenic-derived nitrogen (δ 15 N > 17‰ and ~ 3% N content) at depths and locations close to nutrient sources, particularly at times of the year when large wastewater discharges occur. Harvesting of drift macroalgae could be a cost-effective solution for offsetting nitrogen inputs from anthropogenic sources, but it will be important to first investigate whether harvesting results in negative impacts to associated fauna or nutrient cycling.

Outpatient glucocorticoid use and COVID-19 outcomes: a population-based study - Almudena Rodríguez-Fernández; Irene Visos-Varela; Maruxa Zapata-Cachafeiro; Samuel Pintos-Rodríguez; Rosa M. García-Álvarez; Teresa M. Herdeiro; María Piñeiro-Lamas; Adolfo Figueiras; Ángel Salgado-Barreira; Rosendo Bugarín-González; Eduardo Carracedo-Martínez; Rosa M García-Álvarez; et al. (Inflammopharmacology, 2024)
Introduction Owing to controversy information surrounds effect of glucocorticoids on the evolution of COVID-19, we evaluate the effects of outpatient glucocorticoid use on the severity and progression of COVID-19 and risk of infection and analyse the effect of window of exposure and dose. Methods We conducted a population-based case − control study, involving 4 substudies: (i) Hospitalisation; (ii) Mortality, using subjects hospitalised with a PCR + as cases and subjects without a PCR + as controls; (iii) Progression, including subjects with a PCR + (hospitalised versus non-hospitalised); and (iv) Susceptibility, with all subjects with a PCR + and subjects without a PCR + . Adjusted odds ratios (ORa) and their 95% confidence intervals (95% CI) were calculated. Results The outpatient glucocorticoid use was associated with an increased risk of hospitalisation (aOR 1.79; 95% CI 1.56–2.05), mortality (aOR 2.30; 95% CI 1.68–3.15), progression (aOR 1.69; 95% CI 1.43–2.00) and susceptibility (aOR 1.29, 95% CI 1.19–1.41). Furthermore, the effects was observed to be greater at higher doses and the closer that drug use approached the outcome date, with an almost fourfold increase in mortality among users in the previous month (aOR 3.85; 95% CI 2.63–5.62). Conclusions According to the results of this real-world data study, outpatient glucocorticoid use should be considered in making decisions about intrahospital treatment.

Cooling rate modifies the location of aquaporin 3 in spermatozoa of sheep and goat - Belén Pequeño; María Gemma Millán de la Blanca; Cristina Castaño; Adolfo Toledano-Díaz; Milagros Cristina Esteso; Esther Alba; Francisco A. Arrebola; Rodolfo Ungerfeld; Belén Martínez-Madrid; Manuel Alvarez-Rodriguez; Heriberto Rodriguez-Martinez; Julián Santiago-Moreno (Theriogenology, 2024)

Spatially heterogeneous discharge of glacial meltwater to drainages surrounding the ablating Coropuna ice cap, Peruvian Andes - Elizabeth J. Olson; Lisa R. Welp; Marty D. Frisbee; Sebastián A. Zúñiga Medina; Odiney Alvarez-Campos; Wendy R. Roque Quispe; Carol I. Salazar Mamani; Midhuar R. Arenas Carrión; José Diaz Rodriguez; Juan Manuel Jara Gonzalez; Alexander Ccanccapa-Cartagena; Chad T. Jafvert (Hydrological Sciences Journal, 2024)

Total CO2 budget estimate and degassing dynamics for an active stratovolcano: Turrialba Volcano, Costa Rica - Kate M. Nelson; Christofer Jiménez; Chad D. Deering; Maarten J. de Moor; Joshua M. Blackstock; Stephen P. Broccardo; Florian M. Schwandner; Joshua B. Fisher; Snehamoy Chatterjee; Guillermo Alvarado Induni; Alejandro Rodriguez; Doménicca Guillén Pachacama; et al. (Journal of Volcanology and Geothermal Research, 2024)

Ensemble machine learning using hydrometeorological information to improve modeling of quality parameter of raw water supplying treatment plants - Christian Ortiz-Lopez; Christian Bouchard; Manuel J. Rodriguez (Journal of Environmental Management, 2024)

Wide climatic niche breadth and traits associated with climatic tolerance facilitate eucalypt occurrence in cities worldwide - Manuel Esperon‐Rodriguez; Mark G. Tjoelker; Jonathan Lenoir; Bree Laugier; Rachael V. Gallagher (Global Ecology and Biogeography, 2024)
Aim Eucalypts are important and popular urban tree species across cities worldwide. However, little is known about how their climatic niche breadth (CNB) and functional traits predict their success, and vulnerability, to current climate change in cities. We assessed the relationship between the CNB of eucalypts and key traits to understand their tolerance to climate change. Location Global urban areas, 66 cities in 21 countries. Time period 1981 to 2022. Major species studied Fifty ‘eucalypt’ species belonging to the genera Eucalyptus , Angophora and Corymbia . Methods We used the species' safety margin concept to determine cities where eucalypts were planted outside the limits of their CNB, as defined from the native range, considering two extreme variables, maximum temperature of the warmest month (MTWM) and precipitation of the driest month (PDM). We assessed correlations between functional traits (leaf δ 13 C, leaf dry mass, leaf length, leaf N per dry mass, wood density) and negative safety margins, indicative of tolerance to non‐native conditions. Results In total, 42 species planted in 40 cities exceeded their safety margins for MTWM, while 43 species in 38 cities exceeded their safety margins for PDM. Within 24 cities, all species exceeded their native CNB for both MTWM and PDM. The cities of Atakpame (Togo), Chennai (India), Chongqing (China) and the US cities of Phoenix and Riverside had the highest richness of eucalypt species growing outside their native CNB. Broadly, species with wide CNB, small leaves, high δ 13 C, high leaf N per dry mass and high wood density were more likely to persist in cities where climatic conditions exceeded their native CNB. Main conclusions Eucalypts occupy many cities experiencing climatic conditions outside their native CNB. Species with traits characteristic of heat and drought tolerance are more often planted in cities where climatic conditions may exceed their CNB native limits.

Closing the energy flexibility gap: Enriching flexibility performance rating of buildings with monitored data - Manuel de-Borja-Torrejon; Gerard Mor; Jordi Cipriano; Angel-Luis Leon-Rodriguez; Thomas Auer; Jenny Crawley (Energy and Buildings, 2024)

Economic, environmental, and energy equity convergence: Evidence of a multi-speed Europe? - Manuel Llorca; Ana Rodriguez-Alvarez (Ecological Economics, 2024)

Extracellular cAMP and MRP4 activity influence in vitro capacitation and fertilizing ability of pig spermatozoa - Marcella Spinaci; Olga Blanco-Prieto; Jose Manuel Ortiz-Rodriguez; Chiara Bernardini; Diego Bucci (Research in Veterinary Science, 2024)

Homogeneous vs. heterogeneous photo-Fenton elimination of antibiotic-resistant bacteria bearing intracellular or extracellular resistance: Do resistance mechanisms interfere with disinfection pathways? - Jeremie Decker; Truong-Thien Melvin Le; Jose Manuel Entenza; Isabel del Castillo Gonzalez; Aurelio Hernandez Lehmann; Cesar Pulgarin; Jorge Rodriguez-Chueca; Stefanos Giannakis (Journal of Environmental Chemical Engineering, 2024)

Spatio-temporal trends of mercury levels in alluvial gold mining spoils areas monitored between rainy and dry seasons in the Peruvian Amazon - Edwin Becerra-Lira; Liset Rodriguez-Achata; Adenka Muñoz Ushñahua; Ronald Corvera Gomringer; Evert Thomas; Jorge Garate-Quispe; Litcely Hilares Vargas; Pedro Romel Nascimento Herbay; Luis Alfredo Gamarra Miranda; Eleuterio Umpiérrez; Juan Antonio Guerrero Barrantes; Martin Pillaca; et al. (Environmental Research, 2024)

Heterogeneous Photocatalysis for Efficient Degradation of Lamivudine and Zidovudine Antiretroviral Drugs: Assessment Toxicological in Carrot and Tomato Seeds - Alex Leandro Andrade de Lucena; Marta Maria Menezes Bezerra Duarte; Joan Manuel Rodriguez-Diaz; Rayany Magali da Rocha Santana; Émerson Felipe Mendonça da Silva; Marcos André Soares de Oliveira; Luciano Costa Almeida; Daniella Carla Napoleão (Water, Air, & Soil Pollution, 2024)

Single-Cell Transcriptional Profiling and Gene Regulatory Network Modeling in Tg2576 Mice Reveal Gender-Dependent Molecular Features Preceding Alzheimer-Like Pathologies - Muhammad Ali; Oihane Uriarte Huarte; Tony Heurtaux; Pierre Garcia; Beatriz Pardo Rodriguez; Kamil Grzyb; Rashi Halder; Alexander Skupin; Manuel Buttini; Enrico Glaab (Molecular Neurobiology, 2024)
Alzheimer’s disease (AD) onset and progression is influenced by a complex interplay of several environmental and genetic factors, one of them gender. Pronounced gender differences have been observed both in the relative risk of developing AD and in clinical disease manifestations. A molecular level understanding of these gender disparities is still missing, but could provide important clues on cellular mechanisms modulating the disease and reveal new targets for gender-oriented disease-modifying precision therapies. We therefore present here a comprehensive single-cell analysis of disease-associated molecular gender differences in transcriptomics data from the neocortex, one of the brain regions most susceptible to AD, in one of the most widely used AD mouse models, the Tg2576 model. Cortical areas are also most commonly used in studies of post-mortem AD brains. To identify disease-linked molecular processes that occur before the onset of detectable neuropathology, we focused our analyses on an age with no detectable plaques and microgliosis. Cell-type specific alterations were investigated at the level of individual genes, pathways, and gene regulatory networks. The number of differentially expressed genes (DEGs) was not large enough to build context-specific gene regulatory networks for each individual cell type, and thus, we focused on the study of cell types with dominant changes and included analyses of changes across the combination of cell types. We observed significant disease-associated gender differences in cellular processes related to synapse organization and reactive oxygen species metabolism, and identified a limited set of transcription factors, including Egr1 and Klf6 , a s key regulators of many of the disease-associated and gender-dependent gene expression changes in the model. Overall, our analyses revealed significant cell-type specific gene expression changes in individual genes, pathways and sub-networks, including gender-specific and gender-dimorphic changes in both upstream transcription factors and their downstream targets, in the Tg2576 AD model before the onset of overt disease. This opens a window into molecular events that could determine gender-susceptibility to AD, and uncovers tractable target candidates for potential gender-specific precision medicine for AD.

Assessing the economic implications of climate change impacts on the Paraguayan agricultural sector - Angel Manuel Benitez Rodriguez; Rayan Wolf; Ian Michael Trotter; Angelo Costa Gurgel (Climate and Development, 2024)

Bottom fishing beyond trawling. Spatio-temporal trends of mobile and static bottom fisheries on benthic habitats - Ulla Fernandez-Arcaya; Augusto Rodríguez-Basalo; Patricia Verísimo; José Rodriguez; Elvira Ceballos; Jose Manuel Gonzalez-Irusta; Ana García-Alegre; Maider Plaza-Morlote; Alberto Serrano; Antonio Punzón (Marine Policy, 2024)

Metabolic Determinants of Cerebellar Circuit Formation and Maintenance - Manuel Gonzalez-Rodriguez; Isaac Marin-Valencia (The Cerebellum, 2023)

Modulation of the lipolysis and subsequent antibacterial activity of the fat from black soldier fly (Hermetia illucens) by the combined selection of slaughtering, drying and defatting methods of the larvae - Raúl Hurtado-Ribeira; Jose Manuel Silvan; Tiziana Fornari; Luis Vázquez; Adolfo J. Martinez-Rodriguez; Diana Martin (Innovative Food Science & Emerging Technologies, 2023)

Effect of phage therapy on survival, histopathology, and water microbiota of Penaeus vannamei challenged with Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease (AHPND) - Jean Pierre González-Gómez; Sonia A. Soto-Rodriguez; Bruno Gomez-Gil; Juan Manuel Serrano-Hernández; Rodolfo Lozano-Olvera; Osvaldo López-Cuevas; Nohelia Castro-del Campo; Cristobal Chaidez (Aquaculture, 2023)

Design recommendations for the rehabilitation of an urban canyon in a subtropical climate region using aerial thermography and simulation tools - Marta Videras Rodriguez; Sergio Gomez Melgar; Jose Manuel Andujar Marquez (Energy and Buildings, 2023)

Detection of SARS-CoV-2 in high-efficiency particulate air (HEPA) filters of low-cost air purifiers in community-based organizations - Rachel D. Clarke; Nana Aisha Garba; Manuel A. Barbieri; Leonardo Acuna; Marianna Baum; Maribel Saad Rodriguez; Hansel Frias; Paulina Saldarriaga; Troy Stefano; Kalai Mathee; Giri Narasimhan; David R. Brown (Environmental Monitoring and Assessment, 2023)
This study aims to investigate the presence of SARS-CoV-2 in public spaces and assess the utility of inexpensive air purifiers equipped with high-efficiency particulate air (HEPA) filters for viral detection. Samples were collected from six community-based organizations in underserved minority neighborhoods in Northwest Miami, Florida, from February to May 2022. Reverse transcription–quantitative polymerase chain reaction (RT-qPCR) was used to detect SARS-CoV-2 in air purifier filters and surface swabs. Among 32 filters tested, three yielded positive results, while no positive surface swabs were found. Notably, positive samples were obtained exclusively from child daycare centers. These findings highlight the potential for airborne transmission of SARS-CoV-2 in indoor air, particularly in child daycare centers. Moreover, the study demonstrates the effectiveness of readily available HEPA filters in detecting the virus. Improving indoor ventilation and implementing air filtration systems are crucial in reducing COVID-19 transmission where people gather. Air filtration systems incorporating HEPA filters offer a valuable approach to virus detection and reducing transmission risks. Future research should explore the applicability of this technology for early identification and mitigation of viral outbreaks.

Causality methods to study the functional connectivity in brain networks: the basal ganglia – thalamus causal interactions - Clara Rodriguez-Sabate; Albano Gonzalez; Juan Carlos Perez-Darias; Ingrid Morales; Miguel Sole-Sabater; Manuel Rodriguez (Brain Imaging and Behavior, 2023)
This study uses methods recently developed to study the complex evolution of atmospheric phenomena which have some similarities with the dynamics of the human brain. In both cases, it is possible to record the activity of particular centers (geographic regions or brain nuclei) but not to make an experimental modification of their state. The study of “causality”, which is necessary to understand the dynamics of these complex systems and to develop robust models that can predict their evolution, is hampered by the experimental restrictions imposed by the nature of both systems. The study was performed with data obtained in the thalamus and basal ganglia of awake humans executing different tasks. This work studies the linear, non-linear and more complex relationships of these thalamic centers with the cortex and main BG nuclei, using three complementary techniques: the partial correlation regression method, the Gaussian process regression/distance correlation and a model-free method based on nearest-neighbor that computes the conditional mutual information. These causality methods indicated that the basal ganglia present a different functional relationship with the anterior-ventral (motor), intralaminar and medio-dorsal thalamic centers, and that more than 60% of these thalamus-basal ganglia relationships present a non-linear dynamic (35 of the 57 relationships found). These functional interactions were observed for basal ganglia nuclei with direct structural connections with the thalamus (primary somatosensory and motor cortex, striatum, internal globus pallidum and substantia nigra pars reticulata), but also for basal ganglia without structural connections with the thalamus (external globus pallidum and subthalamic nucleus). The motor tasks induced rapid modifications of the thalamus-basal ganglia interactions. These findings provide new perspectives of the thalamus - BG interactions, many of which may be supported by indirect functional relationships and not by direct excitatory/inhibitory interactions.

Matrix changes driven by cultivar diversity, inulin addition and drying techniques - shaping the antioxidant, antimicrobial and anti-inflammatory properties of blueberry powders - Jessica Brzezowska; Adolfo J. Martinez-Rodriguez; Jose Manuel Silvan; Grzegorz P. Łysiak; Aneta Wojdyło; Krzysztof Lech; Anna Michalska-Ciechanowska (Innovative Food Science & Emerging Technologies, 2023)

Full-scale multisampling and empirical modeling of DBPs in water and air of indoor pools - Elham Ahmadpour; Ianis Delpla; Maximilien Debia; Sabrina Simard; François Proulx; Jean-Baptiste Sérodes; Isabelle Valois; Robert Tardif; Sami Haddad; Manuel Rodriguez (Environmental Monitoring and Assessment, 2023)

Miocene tropical storms: Carbonate framework approaches and geochemistry proxies in a reservoir model - Orangel Aguilera; Olga M. Oliveira De Araújo; Ricardo Tadeu Lopes; Marcelo Cohen; Dayana Alvarado Sierra; Beatriz Teixeira Guimarães; Ana Paula Linhares; Félix Rodriguez; Manuel Moreira; Rut Díaz; Hamilton Santos Gama Filho; Marcelino Jose Dos Anjos; et al. (Marine and Petroleum Geology, 2023)

Life history and stock synthesis assessment of Prionotus punctatus (Teleostei, Triglidae) in southern Brazil - Andrea Renata Rodriguez; Manuel Haimovici; Eidi Kikuchi; Rodrigo Sant'Ana; Bruno L. Mourato; Jose Angel Alvarez Perez; Luís Gustavo Cardoso (Fisheries Management and Ecology, 2023)
Age, growth, and maturity of the bluewing searobin Prionotus punctatus were studied to assess its stock status in southern Brazil. Total length compositions, weight, sex, and maturity stage were recorded from commercial landings, and ages were estimated from transverse sections of the sagittal otolith. The oldest observed specimen was a 12‐year‐old female. Females grew to a larger asymptotic length ( L ∞ = 384.4 mm) than males ( L ∞ = 311.7 mm) but at a slower instantaneous rate ( k females = 0.41 year −1 , k males = 0.75 year −1 ). Reproduction occurred from spring to early fall. Females size‐ and age‐at‐maturity was estimated at 246.8 mm and 1.66 years, while males were at 237.2 mm and 1.38 years. Based on a statistical catch‐at‐age stock assessment, the spawning biomass declined 84% from 1976 to 2000 being classified as overfished and suffering from overfishing (B/B msy = 0.62; F/ Fmsy >1). P. punctatus was regularly discarded by industrial fisheries before 2000 but suffered from high exploitation in the last decades. These results highlight the need for the species to be included in Brazil's fishery management plans.

Metals and metalloids in high-altitude Pyrenean lakes: sources and distribution in pre-industrial and modern sediments - Azibar Rodriguez-Iruretagoiena; Ainara Gredilla; Silvia Fdez-Ortiz de Vallejuelo; Gorka Arana; Maite Meaurio; Juan Manuel Madariaga; Jean Christophe Auguet; Aridane González González; Oleg S. Pokrovsky; Luis Camarero; Alberto de Diego (Environmental Science and Pollution Research, 2023)
High-altitude Pyrenean lakes are ecosystems far from local pollution sources, and thus they are particularly sensitive to the atmospheric deposition of metals and metalloids. This study aims to quantify the effect of human activity in 18 lakes located in both side of the France–Spain frontier. Sediment cores were collected in summer 2013, sampled at a 1cm resolution and the concentration of 24 elements was measured by ICP-MS. Statistic and chemometric analysis of the results highlights the influence of the geographical position and lithogenic features of each lake basin on trapping pollutants. More than the 80% of the lakes showed values of enrichment factor (EF) above 2 for at least one of the elements investigated in at least one core interval, which corroborates the existence of historical anthropogenic inputs of elements in the studied area. The results demonstrate the natural origin of As and Ti in Pyrenees, together with the significant anthropogenic inputs of Cd, Pb, Sb and Sn from ancient times. The data set points mining activities as the main historical source of pollution and illustrate the large impact of the industrial revolution. The regional variability could reflect also differential long-range transport, followed by dry or wet deposition.

Spatiotemporal optimization of water quality degradation monitoring in water distribution systems supplied by surface sources: A chronological and critical review - Andres Ardila; Manuel J. Rodriguez; Geneviève Pelletier (Journal of Environmental Management, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Digital water: artificial intelligence and soft computing applications for drinking water quality assessment - Gyan Chhipi-Shrestha; Haroon R. Mian; Saeed Mohammadiun; Manuel Rodriguez; Kasun Hewage; Rehan Sadiq (Clean Technologies and Environmental Policy, 2023)

Efficient microbial cellulose/Fe3O4 nanocomposite for photocatalytic degradation by advanced oxidation process of textile dyes - Rayany Magali da Rocha Santana; Daniella Carla Napoleão; Joan Manuel Rodriguez-Diaz; Rayssa Kelen de Mendonça Gomes; Marina Gomes Silva; Victor Marcelo Estolano de Lima; Antônio Acacio de Melo Neto; Glória Maria Vinhas; Marta Maria Menezes Bezerra Duarte (Chemosphere, 2023)

Tree crown traits and planting context contribute to reducing urban heat - Mahmuda Sharmin; Mark G. Tjoelker; Sebastian Pfautsch; Manuel Esperon-Rodriguez; Paul D. Rymer; Sally A. Power (Urban Forestry & Urban Greening, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Urban tree inventories as a tool to assess tree growth and failure: The case for Australian cities - Manuel Esperon-Rodriguez; Desi Quintans; Paul D. Rymer (Landscape and Urban Planning, 2023)

Original nanostructured bacterial cellulose/pyrite composite: Photocatalytic application in advanced oxidation processes - Rayany Magali da Rocha Santana; Daniella Carla Napoleão; Joan Manuel Rodriguez-Diaz; Rayssa Kelen de Mendonça Gomes; Marina Gomes Silva; Ramón Raudel Peña Garcia; Glória Maria Vinhas; Marta Maria Menezes Bezerra Duarte (Chemosphere, 2023)

The HL-60 human promyelocytic cell line constitutes an effective in vitro model for evaluating toxicity, oxidative stress and necrosis/apoptosis after exposure to black carbon particles and 2.45 GHz radio frequency - Rosa Ana Sueiro Benavides; José Manuel Leiro-Vidal; J. Antonio Rodriguez-Gonzalez; Francisco J. Ares-Pena; Elena López-Martín (Science of The Total Environment, 2023)

A case-based reasoning tool to recommend drinking water source protection actions - Jérôme Cerutti; Irène Abi-Zeid; Luc Lamontagne; Roxane Lavoie; Manuel J. Rodriguez-Pinzon (Journal of Environmental Management, 2023)

Assessment of rain event effects on source water quality degradation and subsequent water treatment operations - Ianis Delpla; Christian Bouchard; Caetano Dorea; Manuel J. Rodriguez (Science of The Total Environment, 2023)

Appraisal of machine learning techniques for predicting emerging disinfection byproducts in small water distribution networks - Guangji Hu; Haroon R. Mian; Saeed Mohammadiun; Manuel J. Rodriguez; Kasun Hewage; Rehan Sadiq (Journal of Hazardous Materials, 2023)

Detecting mass sediment transport and movement tainted by decades of mining activities in river Quito, Western Colombia - José Marrugo-Negrete; P.F. Rodriguez-Espinosa; P. Godwyn-Paulson; Roberth J. Paternina-Uribe; Mareley Y. Ibarguen Amud; Mauricio Rosso-Pinto; German Enamorado-Montes; Ivan Urango-Cardenas; Harry Gutierrez-Mosquera; Manuel Haminton Salas-Moreno; Carlos Salazar-Camacho; Leonomir Córdoba-Tovar; et al. (Journal of Cleaner Production, 2023)

Preparation, characterization, and antioxidant activity of β-cyclodextrin nanoparticles loaded Rosa damascena essential oil for application in beverage - Zahra Hadian; Mahdie Kamalabadi; Yuthana Phimolsiripol; Balamuralikrishnan Balasubramanian; Jose Manuel Lorenzo Rodriguez; Amin Mousavi Khaneghah (Food Chemistry, 2023)

Global assessment of chemical quality of drinking water: The case of trihalomethanes - Cristina M Villanueva; Iro Evlampidou; Fathelrahman Ibrahim; Carolina Donat-Vargas; Antonia Valentin; Anca-Maria Tugulea; Shinya Echigo; Dragana Jovanovic; Albert T Lebedev; Mildred Lemus-Pérez; Manuel Rodriguez-Susa; Arben Luzati; et al. (Water Research, 2023)

Drinking water management strategies for distribution networks: An integrated performance assessment framework - Haroon R. Mian; Guangji Hu; Kasun Hewage; Manuel J. Rodriguez; Rehan Sadiq (Journal of Environmental Management, 2023)

Domestic water security in the Arctic: A scoping review - Alexandra Cassivi; Anna Covey; Manuel J. Rodriguez; Stéphanie Guilherme (International Journal of Hygiene and Environmental Health, 2023)

Comparison of sampling collection strategies for assessing airborne trichloramine levels in indoor swimming pools - Elham Ahmadpour; Stéphane Hallé; Isabelle Valois; Patrick Eddy Ryan; Sami Haddad; Manuel Rodriguez; Robert Tardif; Maximilien Debia (Environmental Science and Pollution Research, 2022)

Monocyte-to-Lymphocyte Ratio in Clot Analysis as a Marker of Cardioembolic Stroke Etiology - Jesús Juega; Carlos Palacio-Garcia; Maite Rodriguez; Matias Deck; David Rodriguez-Luna; Manuel Requena; Álvaro García-Tornel; Noelia Rodriguez-Villatoro; Marta Rubiera; Sandra Boned; Marian Muchada; Marc Ribo; et al. (Translational Stroke Research, 2022)

Forecasting the daily variability discharge in the fluvial system of the Paraná River: an ODPC hydrology application - Melanie Meis; Manuel Benjamín; Daniela Rodriguez (Hydrological Sciences Journal, 2022)

Degradation of Pollutants from Sanitizer Industries via Advanced Oxidation Processes: Comparison Between Classical and Electrochemical Systems - Naiana Santos Cruz Santana Neves; Vanessa de Oliveira Marques Cavalcanti; Ingrid Larissa da Silva Santana; Maressa Maria de Melo Santos Moura; Isis Henriqueta dos Reis Ferreira; Joan Manuel Rodriguez-Diaz; Mohand Benachour; Daniella Carla Napoleão (Water, Air, & Soil Pollution, 2022)

In vivo subchronic effects of ciguatoxin-related compounds, reevaluation of their toxicity - Sandra Raposo-García; Andrea Boente-Juncal; Mercedes Rodriguez-Vieytes; Mercedes Camiña; Celia Costas; Alejandro Cao; M. Carmen Louzao; Manuel Cifuentes; Carmen Vale; Luis M. Botana (Archives of Toxicology, 2022)
Ciguatoxins are marine compounds that share a ladder-shaped polyether structure produced by dinoflagellates of the genus Gambierdiscus and Fukuyoa , and include maitotoxins (MTX1 and MTX3), ciguatoxins (CTX3C) and analogues (gambierone), components of one of the most frequent human foodborne illness diseases known as ciguatera fish poisoning. This disease was previously found primarily in tropical and subtropical areas but nowadays, the dinoflagellates producers of ciguatoxins had spread to European coasts. One decade ago, the European Food Safety Authority has raised the need to complete the toxicological available data for the ciguatoxin group of compounds. Thus, in this work, the in vivo effects of ciguatoxin-related compounds have been investigated using internationally adopted guidelines for the testing of chemicals. Intraperitoneal acute toxicity was tested for maitotoxin 1 at doses between 200 and 3200 ng/kg and the acute oral toxicity of Pacific Ciguatoxin CTX3C at 330 and 1050 ng/kg and maitotoxin 1 at 800 ng/kg were also evaluated showing not effects on mice survival after a 96 h observation period. Therefore, for the following experiments the oral subchronic doses were between 172 and 1760 ng/kg for gambierone, 10 and 102 ng/kg for Pacific Ciguatoxin CTX3C, 550 and 1760 ng/kg for maitotoxin 3 and 800, 2560 and 5000 ng/kg for maitotoxin 1. The results presented here raise the need to reevaluate the in vivo activity of these agents. Although the intraperitoneal lethal dose of maitotoxin 1 is assumed to be 50 ng/kg, without chemical purity identifications and description of the bioassay procedures, in this work, an intraperitoneal lethal dose of 1107 ng/kg was obtained. Therefore, the data presented here highlight the need to use a common procedure and certified reference material to clearly establish the levels of these environmental contaminants in food.

Novel Methodologies for Providing In Situ Data to HAB Early Warning Systems in the European Atlantic Area: The PRIMROSE Experience - Manuel Ruiz-Villarreal; Marc Sourisseau; Phil Anderson; Caroline Cusack; Patricia Neira; Joe Silke; Francisco Rodriguez; Begoña Ben-Gigirey; Callum Whyte; Solene Giraudeau-Potel; Loic Quemener; Gregg Arthur; et al. (Frontiers in Marine Science, 2022)
Harmful algal blooms (HABs) cause harm to human health or hinder sustainable use of the marine environment in Blue Economy sectors. HABs are temporally and spatially variable and hence their mitigation is closely linked to effective early warning. The European Union (EU) Interreg Atlantic Area project “PRIMROSE”, Predicting Risk and Impact of Harmful Events on the Aquaculture Sector, was focused on the joint development of HAB early warning systems in different regions along the European Atlantic Area. Advancement of the existing HAB forecasting systems requires development of forecasting tools, improvements in data flow and processing, but also additional data inputs to assess the distribution of HAB species, especially in areas away from national monitoring stations, usually located near aquaculture sites. In this contribution, we review different novel technologies for acquiring HAB data and report on the experience gained in several novel local data collection exercises performed during the project. Demonstrations include the deployment of autonomous imaging flow cytometry (IFC) sensors near two aquaculture areas: a mooring in the Daoulas estuary in the Bay of Brest and pumping from a bay in the Shetland Islands to an inland IFC; and several drone deployments, both of Unmanned Aerial Vehicles (UAV) and of Autonomous Surface vehicles (ASVs). Additionally, we have reviewed sampling approaches potentially relevant for HAB early warning including protocols for opportunistic water sampling by coastguard agencies. Experiences in the determination of marine biotoxins in non-traditional vectors and how they could complement standard routine HAB monitoring are also considered.

Alternative tissue fixation for combined histopathological and molecular analysis in a clinically representative setting - Amelia Meecham; Elena Miranda; Hayley T. Morris; Jane Hair; Karin A. Oien; Gareth Gerrard; Naomi Guppy; David Mooney; Emily C. Shaw; Margaret Ashton-Key; Robert Lees; Adrienne Flanagan; et al. (Histochemistry and Cell Biology, 2021)
Formalin is the principal tissue fixative used worldwide for clinical and research purposes. Despite optimal preservation of morphology, its preservation of DNA and RNA is poor. As clinical diagnostics increasingly incorporates molecular-based analysis, the requirement for maintaining nucleic acid quality is of increasing importance. Here we assess an alternative non-formalin-based tissue fixation method, PAXgene Tissue system, with the aim of better preserving nucleic acids, while maintaining the quality of the tissue to be used for vital existing diagnostic techniques. In this study, these criteria are assessed in a clinically representative setting. In total, 203 paired PAXgene Tissue and formalin-fixed samples were obtained. Blind-scored haematoxylin and eosin (H&E) sections showed comparable and acceptable staining. Immunohistochemistry (IHC) staining was suboptimal using existing protocols but improved with minor method adjustment and optimisation. Quality of DNA and RNA was significantly improved by PAXgene tissue fixation [RIN 2.8 versus 3.8 ( p < 0.01), DIN 5.68 versus 6.77 ( p < 0.001)], which translated into improved performance on qPCR assay. These results demonstrate the potential of PAXgene Tissue to be used routinely in place of formalin, maintaining adequate histological staining and significantly improving the preservation of biological molecules in the genomic era.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Interplay between IncF plasmids and topoisomerase mutations conferring quinolone resistance in the Escherichia coli ST131 clone: stability and resistance evolution - Jose-Manuel Rodríguez-Martínez; Lorena Lopez-Cerero; Ana García-Duque; Jesus Rodriguez-Baño; Alvaro Pascual (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
The Escherichia coli ST131 H30 -Rx subclone vehicles CTX-M-15 plasmids and mutations in gyrA and parC conferring multidrug resistance successfully in the clinical setting. The aim of this study was (1) to investigate the relationship of specific topoisomerase mutations on the stability of IncF (CTX-M producing) plasmids using isogenic E. coli mutants and (2) to investigate the impact of the IncF-type plasmids present in the E. coli clone ST131 on the evolution of quinolone resistance. E. coli ATCC 25922 (background strain) and derived mutants encoding specific QRDR substitutions were used. Also, NGS-characterized IncFIA and IncFIB plasmids (encoding CTX-M genes) were included. Plasmid stability was evaluated by sequential dilutions into Luria broth medium without antibiotics for 7 days. Mutant frequency to ciprofloxacin was also evaluated. Moderate differences in the IncF plasmids stability were observed among E. coli ATCC 25922 and isogenic mutants. Under our experimental conditions, the fluctuation of bacteria harboring plasmids was less than 0.5-log (10) in all cases. In the mutant frequency tests, it was observed that the presence of these IncF plasmids increased this value significantly (10–1000-fold). Quinolone resistance substitutions in gyrA or parC genes, frequently found associated with E. coli clone ST131, do not modify the stability of ST131-associated IncFIA and IncFIB plasmids under in vitro conditions. IncF-type plasmids present in E. coli clone ST131 facilitate the selection of resistance to quinolones. These results are consistent with the clinical scenario in which the combination of resistance to quinolones and beta-lactams is highly frequent in the E. coli clone ST131.

Multidrug-resistant Raoultella ornithinolytica misidentified as Klebsiella oxytoca carrying blaOXA β-lactamases: antimicrobial profile and genomic characterization - Iliana Alejandra Cortés-Ortíz; Edgar Mendieta-Condado; Noé Escobar-Escamilla; Julio César Juárez-Gómez; Fabiola Garcés-Ayala; Adnan Araíza Rodriguez; Juan Carlos Bravata-Alcántara; Víctor Hugo Gutiérrez-Muñoz; Juan Manuel Bello-López; José Ernesto Ramírez–González (Archives of Microbiology, 2021)

Sulfur isotope fractionations constrain the biological cycling of dimethylsulfoniopropionate in the upper ocean - Daniela Osorio‐Rodriguez; Manuel Razo‐Mejia; Nathan F. Dalleska; Alex L. Sessions; Victoria J. Orphan; Jess F. Adkins (Limnology and Oceanography, 2021)
The rapid turnover of dimethylsulfoniopropionate (DMSP), likely the most relevant dissolved organic sulfur compound in the surface ocean, makes it pivotal to understand the cycling of organic sulfur. Dimethylsulfoniopropionate is mainly synthesized by phytoplankton, and it can be utilized as carbon and sulfur sources by marine bacteria or cleaved by bacteria or algae to produce the volatile compound dimethylsulfide (DMS), involved in the formation of sulfate aerosols. The fluxes between the consumption (i.e., demethylation) and cleavage pathways are thought to depend on community interactions and their sulfur demand. However, a quantitative assessment of the sulfur partitioning between each of these pathways is still missing. Here, we report for the first time the sulfur isotope fractionations by enzymes involved in DMSP degradation with different catalytic mechanisms, expressed heterologously in Escherichia coli . We show that the residual DMSP from the demethylation pathway is 2.7‰ enriched in δ 34 S relative to the initial DMSP, and that the fractionation factor ( 34 ε ) of the cleavage pathways varies between −1 and −9‰. The incorporation of these fractionation factors into mass balance calculations constrains the biological fates of DMSP in seawater, supports the notion that demethylation dominates over cleavage in marine environments, and could be used as a proxy for the dominant pathways of degradation of DMSP by marine microbial communities.

Chemical composition of Schinus areira essential oil and antimicrobial action against Staphylococcus aureus - Andrea C. Cutro; M. Victoria Castelli; Silvia N. López; Manuel A. Rosales; Axel Hollmann; Sergio A. Rodriguez (Natural Product Research, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Assessment of the exploitable biomass of thread herring (Opisthonema spp.) in northwestern Mexico - Marcelino Ruiz-Domínguez; Casimiro Quiñonez-Velázquez; Dana Isela Arizmendi-Rodriguez; Víctor Manuel Gómez-Muñoz; Manuel Otilio Nevárez-Martínez (Acta Oceanologica Sinica, 2021)

Stonefly Assemblages as Indicators of Relict North African Mountain Streams (Plecoptera) - Boudjema Samraoui; Gilles Vinçon; Joaquin Marquez-Rodriguez; Hamed A. El-Serehy; Manuel Ferreras-Romero; Noureddine Mostefai; Farrah Samraoui (Wetlands, 2021)

Fine-scale time series surveys reveal new insights into spatio-temporal trends in coral cover (2002–2018), of a coral reef on the Southern Great Barrier Reef - Chris Roelfsema; Eva M. Kovacs; Julie Vercelloni; Kathryn Markey; Alberto Rodriguez-Ramirez; Sebastian Lopez-Marcano; Manuel Gonzalez-Rivero; Ove Hoegh-Guldberg; Stuart R. Phinn (Coral Reefs, 2021)

Comparison of Hydrological Model-Based and Geographical-Based Approaches for Estimating Water Travel Times for Source Water Protection - Flavie St-Pierre; Françoise Tardif; Manuel J. Rodriguez; Geneviève Pelletier (Environmental Processes, 2021)

Influence of the Seasonal Thermocline on the Vertical Distribution of Larval Fish Assemblages Associated with Atlantic Bluefin Tuna Spawning Grounds - Itziar Alvarez; Leif K. Rasmuson; Trika Gerard; Raul Laiz-Carrion; Manuel Hidalgo; John T. Lamkin; Estrella Malca; Carmen Ferra; Asvin P. Torres; Diego Alvarez-Berastegui; Francisco Alemany; Jose M. Quintanilla; et al. (Oceans, 2021)
Temperature is often an important variable influencing the vertical position of fish larvae in the water column. The same species may show different vertical distributions in areas with a strong near-surface seasonal thermocline compared to isothermal near-surface regions. In areas with a strong surface thermocline, tuna larvae show a significant preference for the near-surface warmer layers. Little is known regarding larval tuna vertical distribution in isothermal waters and on the vertical distribution of the associated larval fish assemblages. We conducted vertical stratified sampling using the same methodology and fishing device (MOCNESS) in the two major spawning areas of Atlantic bluefin tuna (BFT): western Mediterranean Sea (MED), characterized by a surface thermocline, and the Gulf of Mexico (GOM) which lacks thermal stratification. Tuna larvae occupied the upper 30 m in both areas, but the average larval depth distribution was consistently deeper in the GOM. In the MED, vertical distribution of larval fish assemblages was explained by temperature, and species such as BFT, Thunnus alalunga, and Ceratoscopelus maderensis, among others, coexist above the thermocline and are separated from species such as Cyclothone braueri and Hygophum spp. (found below the thermocline). In the GOM, the environmental correlates of the vertical distribution of the larvae were salinity and fluorescence. Mesopelagic taxa such as Ceratoscopelus spp. and Cyclothone spp., among others, had a shallower average distribution than Lampanyctus spp., Hygophum spp., and Myctophum spp.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Coral Reef Community Changes in Karimunjawa National Park, Indonesia: Assessing the Efficacy of Management in the Face of Local and Global Stressors - Emma V Kennedy; Julie Vercelloni; Benjamin P Neal; Ambariyanto; Dominic E.P. Bryant; Anjani Ganase; Patrick Gartrell; Kristen Brown; Catherine J.S. Kim; Mu’alimah Hudatwi; Abdul Hadi; Agus Prabowo; et al. (Journal of Marine Science and Engineering, 2020)
Karimunjawa National Park is one of Indonesia’s oldest established marine parks. Coral reefs across the park are being impacted by fishing, tourism and declining water quality (local stressors), as well as climate change (global pressures). In this study, we apply a multivariate statistical model to detailed benthic ecological datasets collected across Karimunjawa’s coral reefs, to explore drivers of community change at the park level. Eighteen sites were surveyed in 2014 and 2018, before and after the 2016 global mass coral bleaching event. Analyses revealed that average coral cover declined slightly from 29.2 ± 0.12% (Standard Deviation, SD) to 26.3 ± 0.10% SD, with bleaching driving declines in most corals. Management zone was unrelated to coral decline, but shifts from massive morphologies toward more complex foliose and branching corals were apparent across all zones, reflecting a park-wide reduction in damaging fishing practises. A doubling of sponges and associated declines in massive corals could not be related to bleaching, suggesting another driver, likely declining water quality associated with tourism and mariculture. Further investigation of this potentially emerging threat is needed. Monitoring and management of water quality across Karimunjawa may be critical to improving resilience of reef communities to future coral bleaching.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Development of a drinking water quality index based on a participatory procedure using mixed multicriteria methods - Anna Scheili; Ianis Delpla; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2020)

Predicting unregulated disinfection by-products in small water distribution networks: an empirical modelling framework - Haroon R. Mian; Gyan Chhipi-Shrestha; Kasun Hewage; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2020)

Automatic Adaptation of Model Neurons and Connections to Build Hybrid Circuits with Living Networks - Manuel Reyes-Sanchez; Rodrigo Amaducci; Irene Elices; Francisco B. Rodriguez; Pablo Varona (Neuroinformatics, 2020)

Influence of Organic and Chemical Fertilisation on Antioxidant Compounds Profiles and Activities in Fruits of Fragaria ananassa var. Camarosa - Ariel Aguilera; Gonzalo Tereucán; Stefano Ercoli; Pablo Cornejo; Manuel Rodriguez Gomez; Lars Uhlmann; Claudia Guigas; Tuba Esatbeyoglu; Antonieta Ruiz (Journal of Soil Science and Plant Nutrition, 2020)

Downscaling projections of climate change in Sao Tome and Principe Islands, Africa - Sin Chan Chou; André de Arruda Lyra; Jorge Luís Gomes; Daniel Andrés Rodriguez; Minella Alves Martins; Nicole Costa Resende; Priscila da Silva Tavares; Claudine Pereira Dereczynski; Isabel Lopes Pilotto; Alessandro Marques Martins; Luís Felipe Alves de Carvalho; José Luiz Lima Onofre; et al. (Climate Dynamics, 2020)

Ecogenomics of the SAR11 clade - Jose M. Haro‐Moreno; Francisco Rodriguez‐Valera; Riccardo Rosselli; Francisco Martinez‐Hernandez; Juan J. Roda‐Garcia; Monica Lluesma Gomez; Oscar Fornas; Manuel Martinez‐Garcia; Mario López‐Pérez (Environmental Microbiology, 2020)
Summary Members of the SAR11 clade, despite their high abundance, are often poorly represented by metagenome‐assembled genomes. This fact has hampered our knowledge about their ecology and genetic diversity. Here we examined 175 SAR11 genomes, including 47 new single‐amplified genomes. The presence of the first genomes associated with subclade IV suggests that, in the same way as subclade V, they might be outside the proposed Pelagibacterales order. An expanded phylogenomic classification together with patterns of metagenomic recruitment at a global scale have allowed us to define new ecogenomic units of classification (genomospecies), appearing at different, and sometimes restricted, metagenomic data sets. We detected greater microdiversity across the water column at a single location than in samples collected from similar depth across the global ocean, suggesting little influence of biogeography. In addition, pangenome analysis revealed that the flexible genome was essential to shape genomospecies distribution. In one genomospecies preferentially found within the Mediterranean, a set of genes involved in phosphonate utilization was detected. While another, with a more cosmopolitan distribution, was unique in having an aerobic purine degradation pathway. Together, these results provide a glimpse of the enormous genomic diversity within this clade at a finer resolution than the currently defined clades.

Comparative Study of the Degradation of the Diclofenac Drug Using Photo-Peroxidation and Heterogeneous Photocatalysis with UV-C and Solar Radiation - Dennis Díaz-Rodríguez; María Elena Palacios-Antón; Rayany Magali Da Rocha Santana; Luis Santiago Quiroz-Fernández; Yunet Gómez-Salcedo; Alex Leandro Andrade de Lucena; Daniella Carla Napoleão; Joan Manuel Rodriguez-Diaz (Water, Air, & Soil Pollution, 2020)

Metabolomic analysis of Lavandula dentata L. and Lavandula stoechas L. extracts by LC-QTOF/MS experiments and multivariate analysis techniques as a chemotaxonomical tool - José Pérez-del Palacio; Caridad Díaz-Navarro; Ariadna Martín-Blázquez; Carmen González-Olmedo; Noemí Vergara-Segura; Francesca Algieri; Alba Rodriguez-Nogales; M. Reyes González-Tejero; Manuel Casares-Porcel; Joaquín Molero-Mesa; M. Elena Rodríguez-Cabezas; Olga Genilloud; et al. (Plant Biosystems, 2020)

Synergistic effects of quenching agents and pH on the stability of regulated and unregulated disinfection by-products for drinking water quality monitoring - Jianan Gao; Francois Proulx; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2020)

Annual bacterial community cycle in a seasonally ice‐covered river reflects environmental and climatic conditions - Perrine Cruaud; Adrien Vigneron; Marie‐Stéphanie Fradette; Caetano C. Dorea; Alexander I. Culley; Manuel J. Rodriguez; Steve J. Charette (Limnology and Oceanography, 2020)
Bacteria are key players in biogeochemical cycles and control water quality in freshwater ecosystems. Nevertheless, little is known about the identity and ecology of riverine bacteria, especially during ice‐covered periods that are often mistakenly perceived as periods with negligible biological activities. Here, we analyzed in detail the effects of environmental and climatic conditions on freshwater bacterial community structure and diversity over a 2‐yr sampling campaign, targeting a seasonally ice‐covered river of the Quebec City (Canada) area, the Saint‐Charles River. Quantitative polymerase chain reaction and 16S ribosomal RNA gene high‐throughput sequencing demonstrated a strong seasonal cycle of the bacterial community composition with rapid successions of bacterial lineages, reflecting the harsh climatic condition of the region. During the summer, the bacterial community was dominated by typical freshwater microorganisms such as Limnohabitans , Sporichthyaceae hgcI/acI clade, and Pseudarcicella . In contrast, the results suggest that during the cold season, the low water temperatures, combined with other prevailing conditions such as reduced light availability and minimal particulate inputs from the catchment, created various environmental niches for potential methanotrophic Gammaproteobacteria , such as Crenothrix and Methylobacter , other Betaproteobacteria , such as Candidatus Methylopumilus, Candidatus Nitrotoga, and Rhodoferax, as well as Verrucomicrobia and Parcubacteria . The presence of these taxa in the winter suggests active carbon, iron, and nitrogen cycling under ice, whereas summer lineages are dormant or in a phase of reduced activity. These results increase our understanding of bacterial dynamic and potential metabolic processes occurring in seasonally ice‐covered inland waters, providing evidence that winter can be an especially important period for freshwater ecological processes.

Evaluation of occult hepatitis B infection in tissue donors: a multicenter analysis in Spain - Jacinto Sánchez Ibáñez; Ana Vilarrodona Serrat; Teresa Seoane Pillado; Clara Rodriguez Aierbe; Rafael Villalba Montoro; Javier Calvo Benito; Marta Pevida Lopez; Sergio Fernández Paneque; Elena Vuelta Lopez; Maria Jose Martínez Lorenzo; Manuel González Romero; Angelina Cañizares Castellanos; et al. (Cell and Tissue Banking, 2019)

Protected area downgrading, downsizing, and degazettement as a threat to iconic protected areas - Siyu Qin; Rachel E. Golden Kroner; Carly Cook; Anteneh T. Tesfaw; Rowan Braybrook; Carlos Manuel Rodriguez; Claire Poelking; Michael B. Mascia (Conservation Biology, 2019)
Protected areas (PAs) are expected to conserve nature and provide ecosystem services in perpetuity, yet widespread protected area downgrading, downsizing, and degazettement (PADDD) may compromise these objectives. Even iconic protected areas are vulnerable to PADDD, although these PADDD events are often unrecognized. We identified 23 enacted and proposed PADDD events within World Natural Heritage Sites and examined the history, context, and consequences of PADDD events in 4 iconic PAs (Yosemite National Park, Arabian Oryx Sanctuary, Yasuní National Park, and Virunga National Park). Based on insights from published research and international workshops, these 4 cases revealed the diverse pressures brought on by competing interests to develop or exploit natural landscapes and the variety of mechanisms that enables PADDD. Knowledge gaps exist in understanding of the conditions through which development pressures translate to PADDD events and their impacts, partially due to a lack of comprehensive PADDD records. Future research priorities should include comprehensive regional and country‐level profiles and analysis of risks, impacts, and contextual factors related to PADDD. Policy options to better govern PADDD include improving tracking and reporting of PADDD events, establishing transparent PADDD policy processes, coordinating among legal frameworks, and mitigating negative impacts of PADDD. To support PADDD research and policy reforms, enhanced human and financial capacities are needed to train local researchers and to host publicly accessible data. As the conservation community considers the achievements of Aichi Target 11 and moves toward new biodiversity targets beyond 2020, researchers, practitioners, and policy makers need to work together to better track, assess, and govern PADDD globally.

Climate change scenarios for Paraguayan power demand 2017–2050 - Angel Manuel Benitez Rodriguez; Ian Michael Trotter (Climatic Change, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Halogenated acetaldehydes in water: A review of their occurrence, formation, precursors and control strategies - Jianan Gao; Francois Proulx; Manuel J. Rodriguez (Critical Reviews in Environmental Science and Technology, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Vulnerability of smallholder farmers to climate change in Central America and Mexico: current knowledge and research gaps - Camila I. Donatti; Celia A. Harvey; M. Ruth Martinez-Rodriguez; Raffaele Vignola; Carlos Manuel Rodriguez (Climate and Development, 2019)

Drinking Water Source Monitoring Using Early Warning Systems Based on Data Mining Techniques - Ianis Delpla; Mihai Florea; Manuel J. Rodriguez (Water Resources Management, 2019)

Influence of salinity cycles in bioreactor performance and microbial community structure of membrane-based tidal-like variable salinity wastewater treatment systems - Alejandro Rodriguez-Sanchez; Juan Carlos Leyva-Diaz; Barbara Muñoz-Palazon; Jose Manuel Poyatos; Jesus Gonzalez-Lopez (Environmental Science and Pollution Research, 2019)

Maximum Influent Salinity Affects the Diversity of Mineral-Precipitation-Mediating Bacterial Communities in Membrane Biofilm of Hybrid Moving Bed Biofilm Reactor-Membrane Bioreactor - Alejandro Rodriguez-Sanchez; Barbara Muñoz-Palazon; Miguel Hurtado-Martinez; Maria Angustias Rivadeneyra; Jose Manuel Poyatos; Jesus Gonzalez-Lopez (Water, Air, & Soil Pollution, 2018)

Discovery of a novel iflavirus sequence in the eastern paralysis tick Ixodes holocyclus - Caitlin A. O’Brien; Sonja Hall-Mendelin; Jody Hobson-Peters; Georgia Deliyannis; Andy Allen; Ala Lew-Tabor; Manuel Rodriguez-Valle; Dayana Barker; Stephen C. Barker; Roy A. Hall (Archives of Virology, 2018)

A Novel Application of Indocyanine Green Immunofluorescence in Emergent Colorectal Surgery - Deborah S. Keller; Richard Boulton; Manuel Rodriguez-Justo; Richard Cohen; Manish Chand (Journal of Fluorescence, 2018)

Use of differential absorbance to estimate concentrations of chlorinated disinfection by-product in drinking water: Critical review and research needs - Nicolas Beauchamp; Caetano Dorea; Christian Bouchard; Manuel Rodriguez (Critical Reviews in Environmental Science and Technology, 2018)

Models for estimation of the presence of non-regulated disinfection by-products in small drinking water systems - Stéphanie Guilherme; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2017)

Growth and mortality of larval anchoveta Engraulis ringens , in northern Chile during winter and their relationship with coastal hydrographic conditions - Jorge E. Contreras; Camilo Rodriguez‐Valentino; Mauricio F. Landaeta; Guido Plaza; Manuel I. Castillo; Mónica Alvarado‐Niño (Fisheries Oceanography, 2017)
Larval growth, age, growth effect and instantaneous mortality were estimated in anchoveta, Engraulis ringens , collected biweekly during the austral winter of 2014 in nearshore waters off Bay of Antofagasta (23°41′W–70°30′S), northern Chile. Through measuring standard length ( SL ) and sagitta microstructure analysis, it was estimated that the growth rate of E. ringens larvae decreased from June (0.85 mm day −1 ) to August (0.50 mm day −1 ). However, the water temperature was homogeneous during the sampling dates (14.6, 15.2, 14.4, and 14.6°C), suggesting that the decelerating larval growth was not linked to changes in sea temperature. Additionally, larvae with slow growth have larger otoliths compared with conspecifics with fast growth (growth effect). Larval mortality rates tended to decrease until the middle of July (0.18 per day) but increased to 0.25 per day in early August, which coincided with lower food availability (i.e., chlorophyll‐a, 2.7–5.6 mg m −3 ) and a high occurrence of smaller larvae (1.58–11.5 mm). Partial least squares analysis indicates low covariance between the biological and oceanographic variables ( PLS : 11.71%), suggesting that other factors, such as parental effects, may explain the abrupt decrease in the larval growth rates.

Minimizing the impacts of contaminant intrusion in small water distribution networks through booster chlorination optimization - Nilufar Islam; Manuel J. Rodriguez; Ashraf Farahat; Rehan Sadiq (Stochastic Environmental Research and Risk Assessment, 2017)

Small drinking water systems under spatiotemporal water quality variability: a risk-based performance benchmarking framework - Ty Bereskie; Husnain Haider; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

Drinking Water Management and Governance in Canada: An Innovative Plan-Do-Check-Act (PDCA) Framework for a Safe Drinking Water Supply - Ty Bereskie; Manuel J. Rodriguez; Rehan Sadiq (Environmental Management, 2017)

Risk-based framework for optimizing residual chlorine in large water distribution systems - Muhammad Nadeem Sharif; Ashraf Farahat; Husnain Haider; Muhammad A. Al-Zahrani; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

Small shifts in microsite occupation could mitigate climate change consequences for mountain top endemics: a test analyzing saxicolous lichen distribution patterns - Juan Manuel Rodriguez; Daniel Renison; Edith Filippini; Cecilia Estrabou (Biodiversity and Conservation, 2017)

The functional connectivity in the motor loop of human basal ganglia - Clara Rodriguez-Sabate; Magdalena Sabate; Catalina Llanos; Ingrid Morales; Alberto Sanchez; Manuel Rodriguez (Brain Imaging and Behavior, 2017)

Plankton carbon metabolism and air–water CO 2 fluxes at a hypereutrophic tropical estuary - Mariana Guenther; Moacyr Araújo; Carlos Noriega; Manuel Flores‐Montes; Eliane Gonzalez‐Rodriguez; Sigrid Neumann‐Leitão (Marine Ecology, 2017)
Multiple biotic and abiotic drivers regulate the balance between CO 2 assimilation and release in surface waters. In the present study, we compared in situ measurements of plankton carbon metabolism (primary production and respiration) to calculated air–water CO 2 fluxes (based on abiotic parameters) during 1 year (2008) in a hypereutrophic tropical estuary (Recife Harbor, NE Brazil – 08°03′S, 34°52′W) to test the hypothesis that high productivity leads to a net CO 2 flux from the atmosphere. The calculated CO 2 fluxes through the air–water interface (FCO 2 ) were negative throughout the year (FCO 2 : –2 to –9 mmol C·m −2 ·day −1 ), indicating that Recife Harbor is an atmospheric CO 2 sink. Respiration rates of the plankton community ranged from 2 to 45 mmol C·m −2 ·hr −1 . Gross primary production ranged from 0.2 to 281 mmol C·m −2 ·hr −1 , exceeding respiration during most of the year (net autotrophy), except for the end of the wet season, when the water column was net heterotrophic. The present results highlight the importance of including eutrophic tropical shallow estuaries in global air–water CO 2 flux studies, in order to better understand their role as a sink of atmospheric CO 2 .

What information do policy makers need to develop climate adaptation plans for smallholder farmers? The case of Central America and Mexico - Camila I. Donatti; Celia A. Harvey; M. Ruth Martinez-Rodriguez; Raffaele Vignola; Carlos Manuel Rodriguez (Climatic Change, 2017)

Theoretical insights into [NiFe]-hydrogenases oxidation resulting in a slowly reactivating inactive state - Raffaella Breglia; Manuel Antonio Ruiz-Rodriguez; Alessandro Vitriolo; Rubén Francisco Gonzàlez-Laredo; Luca De Gioia; Claudio Greco; Maurizio Bruschi (JBIC Journal of Biological Inorganic Chemistry, 2017)

Experimental and DFT characterization, antioxidant and anticancer activities of a Cu(II)–irbesartan complex: structure–antihypertensive activity relationships in Cu(II)–sartan complexes - María S. Islas; Alicia Luengo; Carlos A. Franca; Mercedes Griera Merino; Laura Calleros; Manuel Rodriguez-Puyol; Luis Lezama; Evelina G. Ferrer; Patricia A. M. Williams (JBIC Journal of Biological Inorganic Chemistry, 2016)

Membrane coordination of receptors and channels mediating the inhibition of neuronal ion currents by ADP - Hend Gafar; Manuel Dominguez Rodriguez; Giri K. Chandaka; Isabella Salzer; Stefan Boehm; Klaus Schicker (Purinergic Signalling, 2016)

Optimization of chlorination boosters in drinking water distribution network for Al-Khobar City in Saudi Arabia - Muhammad Nadeem Sharif; Ashraf Farahat; Muhammad A. Al-Zahrani; Nilufar Islam; Manuel J. Rodriguez; Rehan Sadiq (Arabian Journal of Geosciences, 2016)

Integrated Decision Support System for Prognostic and Diagnostic Analyses of Water Distribution System Failures - M. Shafiqul Islam; Rehan Sadiq; Manuel J. Rodriguez; Homayoun Najjaran; Mina Hoorfar (Water Resources Management, 2016)

SNP discovery from liver transcriptome in the fish Piaractus mesopotamicus - Vito Antonio Mastrochirico-Filho; Milene Elissa Hata; Lucas Seiti Sato; Paulo Henrique Jorge; Fausto Foresti; Manuel Vera Rodriguez; Paulino Martínez; Fábio Porto-Foresti; Diogo Teruo Hashimoto (Conservation Genetics Resources, 2016)

Assessing regulatory violations of disinfection by-products in water distribution networks using a non-compliance potential index - Nilufar Islam; Rehan Sadiq; Manuel J. Rodriguez; Christelle Legay (Environmental Monitoring and Assessment, 2016)

IEOOS: the Spanish Institute of Oceanography Observing System - Elena Tel; Rosa Balbin; Jose-Manuel Cabanas; Maria-Jesus Garcia; M. Carmen Garcia-Martinez; Cesar Gonzalez-Pola; Alicia Lavin; Jose-Luis Lopez-Jurado; Carmen Rodriguez; Manuel Ruiz-Villarreal; Ricardo F. Sánchez-Leal; Manuel Vargas-Yáñez; et al. (Ocean Science, 2016)
Since its foundation, 100 years ago, the Spanish Institute of Oceanography (IEO) has been observing and measuring the ocean characteristics. Here is a summary of the initiatives of the IEO in the field of the operational oceanography. Some systems like the tide gauges network has been working for more than 70 years. The standard sections began at different moments depending on the local projects, and nowadays there are more than 180 coastal stations and deep-sea ones that are systematically sampled, obtaining physical and biochemical measurements. At this moment, the Observing System includes six permanent moorings equipped with current meters, an open-sea ocean-meteorological buoy offshore Santander and a sea-surface temperature satellite image station. It also supports the Spanish contribution to the Argo international programme with 47 deployed profilers, and continuous monitoring thermosalinometers, meteorological stations and vessel-mounted acoustic Doppler current profilers on the research vessel fleet. The system is completed with the contribution to the Northwest Iberian peninsula and Gibraltar observatories, and the development of regional prediction models. All these systematic measurements allow the IEO to give responses to ocean research activities, official agencies requirements and industrial and main society demands such as navigation, resource management, risks management, recreation, as well as for management development pollution-related economic activities or marine ecosystems. All these networks are linked to international initiatives, framed largely in supranational programmes of Earth observation sponsored by the United Nations or the European Union. The synchronic observation system permits a spatio-temporal description of some events, such as new deep water formation in the Mediterranean Sea and the injection of heat to intermediate waters in the Bay of Biscay after some colder northern storms in winter 2005.

Modelling the regional variability of the probability of high trihalomethane occurrence in municipal drinking water - Geneviève Cool; Alexandre Lebel; Rehan Sadiq; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2015)

Development, application, and sensitivity analysis of a water quality index for drinking water management in small systems - A. Scheili; Manuel J. Rodriguez; R. Sadiq (Environmental Monitoring and Assessment, 2015)

Estimation of urban water supply issues at the local scale: a participatory approach - Christelle Legay; Geneviève Cloutier; Salem Chakhar; Florent Joerin; Manuel J. Rodriguez (Climatic Change, 2015)

Assessment of the gross primary production dynamics of a Mediterranean holm oak forest by remote sensing time series analysis - Víctor Cicuéndez; Javier Litago; Margarita Huesca; Manuel Rodriguez-Rastrero; Laura Recuero; Silvia Merino-de-Miguel; Alicia Palacios-Orueta (Agroforestry Systems, 2015)

Transducin-like enhancer of split 3 (TLE3) in adipose tissue is increased in situations characterized by decreased PPARγ gene expression - Francisco José Ortega; Marta Serrano; Sergio Rodriguez-Cuenca; José María Moreno-Navarrete; María Gómez-Serrano; Mònica Sabater; Jose Ignacio Rodriguez-Hermosa; Gemma Xifra; Wifredo Ricart; Belén Peral; Antonio Vidal-Puig; José Manuel Fernández-Real (Journal of Molecular Medicine, 2015)

Triple-layered mixed co-culture model of RPE cells with neuroretina for evaluating the neuroprotective effects of adipose-MSCs - David Rodriguez-Crespo; Salvatore Di Lauro; Amar K. Singh; Maria T. Garcia-Gutierrez; Manuel Garrosa; J. Carlos Pastor; Ivan Fernandez-Bueno; Girish K. Srivastava (Cell and Tissue Research, 2014)

Online Drinking Water Quality Monitoring: Review on Available and Emerging Technologies - Muinul H. Banna; Syed Imran; Alex Francisque; Homayoun Najjaran; Rehan Sadiq; Manuel Rodriguez; Mina Hoorfar (Critical Reviews in Environmental Science and Technology, 2014)

Water distribution system failure: a framework for forensic analysis - M. Shafiqul Islam; Rehan Sadiq; Manuel J. Rodriguez; Homayoun Najjaran; Alex Francisque; Mina Hoorfar (Environment Systems and Decisions, 2014)

Optimizing booster chlorination in water distribution networks: a water quality index approach - Nilufar Islam; Rehan Sadiq; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2013)

Spatial and temporal occurrence of N-nitrosamines in seven drinking water supply systems - Isabelle J. Brisson; Patrick Levallois; Hélène Tremblay; Jean Sérodes; Christian Deblois; Jeffrey Charrois; Vincent Taguchi; Jessica Boyd; XingFang Li; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2013)

Evaluating Water Quality Failure Potential in Water Distribution Systems: A Fuzzy-TOPSIS-OWA-based Methodology - M. Shafiqul Islam; Rehan Sadiq; Manuel J. Rodriguez; Homayoun Najjaran; Alex Francisque; Mina Hoorfar (Water Resources Management, 2013)

Human–felid conflict as a further handicap to the conservation of the critically endangered Iberian lynx - Germán Garrote; Guillermo López; José M. Gil-Sánchez; Eva Rojas; Manuel Ruiz; José F. Bueno; Santiago de Lillo; Javier Rodriguez-Siles; José M. Martín; Joaquín Pérez; Maribel García-Tardío; Gerardo Valenzuela; et al. (European Journal of Wildlife Research, 2013)

Modelling geosmin concentrations in three sources of raw water in Quebec, Canada - Julien Parinet; Manuel J. Rodriguez; Jean-Baptiste Sérodes (Environmental Monitoring and Assessment, 2013)

Balance between apoptosis or survival induced by changes in extracellular-matrix composition in human mesangial cells: a key role for ILK-NFκB pathway - María del Nogal; Alicia Luengo; Gemma Olmos; Marina Lasa; Diego Rodriguez–Puyol; Manuel Rodriguez–Puyol; Laura Calleros (Apoptosis, 2012)

New polymorphisms in human MEF2C gene as potential modifier of hypertrophic cardiomyopathy - Cristina Alonso-Montes; Manuel Naves-Diaz; Jose Luis Fernandez-Martin; Julian Rodriguez-Reguero; Cesar Moris; Eliecer Coto; Jorge B. Cannata-Andia; Isabel Rodriguez (Molecular Biology Reports, 2012)

Effect of salinity on egg hatching, yolk sac absorption and larval rearing of Senegalese sole ( Solea senegalensis Kaup 1858) - Emilio A. Salas Leitón; Ana Rodriguez‐Rúa; Esther Asensio; Carlos Infante; Manuel Manchado; Catalina Fernández‐Díaz; José P. Cañavate (Reviews in Aquaculture, 2012)
Assays carried out under laboratory‐controlled conditions revealed that eggs of Senegalese sole, Solea senegalensis Kaup 1858, incubated at 10, 18, 27 and 33 grams per litre (g L −1 ) reached their maximum hatching rates (above 80%) 48 h after incubation. In contrast, hatching was significantly delayed (24 h) and completely failed when the salinity was set at 5 and 0 g L −1 , respectively. Newly hatched and early‐developing yolk sac larvae presented similar survival rates 3 days after hatching (DAH) when exposed to salinities of 10, 18, 27 and 33 g L −1 . Larvae incubated at 5 g L −1 salinity died a few hours after hatching once they were released from their respective chorions. The notochord length was unmodified by salinity 5 DAH. Nevertheless, an overall lower myotomal height and a putative delay in the depletion of yolk sac were found in larvae reared at 10 g L −1 . This anomaly in overall larval development became more pronounced with the occurrence (100% of analysed larvae) of mouth deformities and a lack of functionality under 10 g L −1 salinity. Transferring 2 DAH larvae from 33 g L −1 (exhibiting normal mouth development) to a medium with a salinity of 10 g L −1 had no effect on first feeding, weight and metamorphic index. Overall our results indicate the existence of a key time window (0–2 DAH) in which a salinity value higher than 10 g L −1 is required to achieve adequate mouth development and further functionality of larvae. The present work represents a valuable contribution to the sole industry, opening new possibilities in hatchery management practices.

Light-dependent changes in plastid differentiation influence carotenoid gene expression and accumulation in carrot roots - Paulina Fuentes; Lorena Pizarro; Juan Camilo Moreno; Michael Handford; Manuel Rodriguez-Concepcion; Claudia Stange (Plant Molecular Biology, 2012)

Air quality monitoring system using lichens as bioindicators in Central Argentina - Cecilia Estrabou; Edith Filippini; Juan Pablo Soria; Gabriel Schelotto; Juan Manuel Rodriguez (Environmental Monitoring and Assessment, 2011)

Multi-level modelling of chlorination by-product presence in drinking water distribution systems for human exposure assessment purposes - Christelle Legay; Manuel J. Rodriguez; Luis Miranda-Moreno; Jean-Baptiste Sérodes; Patrick Levallois (Environmental Monitoring and Assessment, 2011)

Assessment of lead exposure in Spanish imperial eagle (Aquila adalberti) from spent ammunition in central Spain - Julia Rodriguez-Ramos Fernandez; Ursula Höfle; Rafael Mateo; Olga Nicolas de Francisco; Rachel Abbott; Pelayo Acevedo; Juan Manuel Blanco (Ecotoxicology, 2011)

Differential Effect of Lactobacillus johnsonii BFE 6128 on Expression of Genes Related to TLR Pathways and Innate Immunity in Intestinal Epithelial Cells - Stephanie Seifert; Manuel Rodriguez Gómez; Bernhard Watzl; Wilhelm H. Holzapfel; Charles M. A. P. Franz; María G. Vizoso Pinto (Probiotics and Antimicrobial Proteins, 2010)

Detection of somaclonal variants in somatic embryogenesis-regenerated plants of Vitis vinifera by flow cytometry and microsatellite markers - María Jesús Prado; Eleazar Rodriguez; Laura Rey; María Victoria González; Conceição Santos; Manuel Rey (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Association of physical activity with muscular strength and fat-free mass in adolescents: the HELENA study - Diego Moliner-Urdiales; Francisco B. Ortega; Germán Vicente-Rodriguez; Juan P. Rey-Lopez; Luis Gracia-Marco; Kurt Widhalm; Michael Sjöström; Luis A. Moreno; Manuel J. Castillo; Jonatan R. Ruiz (European Journal of Applied Physiology, 2010)

Using multi-criteria decision analysis to assess the vulnerability of drinking water utilities - Florent Joerin; Geneviève Cool; Manuel J. Rodriguez; Marc Gignac; Christian Bouchard (Environmental Monitoring and Assessment, 2010)

Stimulation of endothelial progenitor cells: a new putative effect of several cardiovascular drugs - Natália António; Rosa Fernandes; Noela Rodriguez-Losada; Manuel F. Jiménez-Navarro; Artur Paiva; Eduardo de Teresa Galván; Lino Gonçalves; Carlos Fontes Ribeiro; Luís A. Providência (European Journal of Clinical Pharmacology, 2010)

Taxonomic Reassessment of the Genus Padina (Dictyotales, Phaeophyta) from the Gulf of California - Rafael Riosmena-Rodriguez; Litzia Paul-Chavez; Gustavo Hernandez-Carmona; Juan Manuel Lopez-Vivas; Margarita Casas-Valdez (Algae, 2009)

Seroprevalence of Neospora caninum antibodies in beef cattle in three southern states of Mexico - Zeferino Garcia-Vazquez; Rodrigo Rosario-Cruz; Felix Mejia-Estrada; Ivan Rodriguez-Vivas; Dora Romero-Salas; Manuel Fernandez-Ruvalcaba; Carlos Cruz-Vazquez (Tropical Animal Health and Production, 2009)

Communicating human health risks associated with disinfection by-products in drinking water supplies: a fuzzy-based approach - Rehan Sadiq; Manuel J. Rodriguez; Syed A. Imran; Homayoun Najjaran (Stochastic Environmental Research and Risk Assessment, 2007)

Owl monkey MHC-DRB exon 2 reveals high similarity with several HLA-DRB lineages - Carlos F. Suárez; Manuel E. Patarroyo; Esperanza Trujillo; Mónica Estupiñán; Juan E. Baquero; Carlos Parra; Raúl Rodriguez (Immunogenetics, 2006)

Owl monkey MHC-DRB exon 2 reveals high similarity with several HLA-DRB lineages - Carlos F. Suárez; Manuel E. Patarroyo; Esperanza Trujillo; Mónica Estupiñán; Juan E. Baquero; Carlos Parra; Raúl Rodriguez (Immunogenetics, 2006)

Laboratory-scale chlorination to estimate the levels of halogenated DBPs in full-scale distribution systems - Manuel J. Rodriguez; Jean Sérodes (Environmental Monitoring and Assessment, 2005)

Integrated control of Boophilus microplus ticks in Cuba based on vaccination with the anti-tick vaccine Gavac TM - Manuel Rodriguez Valle; Luis Mèndez; Mario Valdez; Miguel Redondo; Carlos Montero Espinosa; Milagro Vargas; Ricardo Lleonart Cruz; Humberto Perez Barrios; Guillermo Seoane; Emerio Serrano Ramirez; Oscar Boue; Jorge Lodos Vigil; et al. (Experimental and Applied Acarology, 2004)

Integrated control of Boophilus microplus ticks in Cuba based on vaccination with the anti-tick vaccine Gavac TM - Manuel rodriguez Valle; Luis Mèndez; Mario Valdez; Miguel Redondo; Carlos montero Espinosa; Milagro Vargas; Ricardo lleonart Cruz; Humberto perez Barrios; Guillermo Seoane; Emerio serrano Ramirez; Oscar Boue; Jorge lodos Vigil; et al. (Experimental and Applied Acarology, 2004)

Mitigation of salt stress in wheat seedlings by a gfp-tagged Azospirillum lipoferum - Macario Bacilio; Hilda Rodriguez; Manuel Moreno; Juan-Pablo Hernandez; Yoav Bashan (Biology and Fertility of Soils, 2004)

Trihalomethanes in Drinking Water of Greater Québec Region (Canada): Occurrence, Variations and Modelling - Manuel J. Rodriguez; Yannick Vinette; Jean-B. Sérodes; Christian Bouchard (Environmental Monitoring and Assessment, 2003)

Pheromone-Based Trapping of West Indian Sugarcane Weevil in a Sugarcane Plantation - Allan C. Oehlschlager; Lilliana Gonzalez; Manuel Gomez; Carlos Rodriguez; Romano Andrade (Journal of Chemical Ecology, 2002)

Sequence and expression of MHC-DPB1 molecules of the New World monkey Aotus nancymaae, a primate model for Plasmodium falciparum - Diana Diaz; Claudia A. Daubenberger; Tatjana Zalac; Raul Rodriguez; Manuel Patarroyo (Immunogenetics, 2002)

Sequence and diversity of MHC DQA and DQB genes of the owl monkey Aotus nancymaae - Diana Diaz; Martin Naegeli; Raul Rodriguez; J. Javier Nino-Vasquez; Alberto Moreno; Manuel Elkin Patarroyo; Gerd Pluschke; Claudia A. Daubenberger (Immunogenetics, 2000)

Death and neuroprotection of retinal ganglion cells after different types of injury - Manuel Vidal-Sanz; Maria Lafuente; Paloma Sobrado-Calvo; Inmaculada SellÉs-Navarro; Elena Rodriguez; Sergio Mayor-Torroglosa; MarÍa P. Villegas-PÉrez (Neurotoxicity Research, 2000)

Sequence and diversity of DRB genes of Aotus nancymaae , a primate model for human malaria parasites - J. Javier Nino-Vasquez; Denise Vogel; Raul Rodriguez; Alberto Moreno; Manuel Elkin Patarroyo; Gerd Pluschke; Claudia A. Daubenberger (Immunogenetics, 2000)

Synthesis and characterization of Sodium cis-dichlorochenodeoxycholylglycinato(O,N) platinum(II) – Cytostatic activity - Julio J. Criado; M.C. Garcia-Moreno; Rocio R. Macias; Jose J.G. Marin; Manuel Medarde; E. Rodriguez-Fernandez (BioMetals, 1999)

Sequence and diversity of T-cell receptor β-chain V and J genes of the owl monkey Aotus nancymaae - William Vecino; Claudia Daubenberger; Raul Rodriguez; Alberto Moreno; Manuel Patarroyo; Gerd Pluschke (Immunogenetics, 1999)